GBIF Occurrence Download - occdownload gbif.org (The Global Biodiversity Information Facility, 2018)
A dataset containing 740753227 species occurrences available in GBIF matching the query: BasisOfRecord: Human Observation
Year: 1960-2018
HasCoordinate: true
HasGeospatialIssue: false. The dataset includes 740753227 records from 10584 constituent datasets:
95 records from Ortelsbruch - Hangmoor bei Morbach.
1562 records from Données d'expertise convention GTM.
53 records from Plasm bearing foraminifera counts from M35/1_MSN1058.
2500 records from Aves of wetlands and protected forests in Benin.
80 records from Total foraminifera counts of multinet M21/4_MSN704.
1355 records from (Table T5) Planktonic foraminifera abundance of ODP Hole 170-1043A sediments.
12 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5110-4.
380 records from Artenvielfalt der Nordsee - Helgoland.
146 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/088-4.
15 records from Hessen-GEO-Tag am Schlossberg von Homberg/Efze.
61991 records from North East Scotland Terrestrial Mammals 1900-2017 (excluding squirrels, wild cats and marine mammals).
135 records from Total foraminifera counts of multinet M21/3_MSN688.
12 records from Range table from planktonic foraminifers in ODP Hole 178-1100D.
423 records from Neogene palynomorpha from site 81-552.
120 records from BIRDRACE The early birds.
1049319 records from WildNet - Queensland Wildlife Data.
1263 records from RECORD Orthoptera Data.
3 records from Benthic foraminifera abundance of Hole 84-566A.
64 records from (Table 6) Abundances of dinoflagellates in ODP Hole 104-642B.
3335 records from Données naturalistes de Fabien LE NOUVEL.
92 records from Nannofossil abundance of Hole 22-218.
2680 records from (Table 14A) Occurrences of planktonic foraminifers in DSDP Hole 90-592, samples 592-1-CC through 592-29-CC.
21 records from City of Edinburgh Natural Heritage Service - Easter Craiglockhart Pond and Marsh Survey..
43 records from Répartition Pelophylax (Eval 2012).
1079 records from Planktic foraminifera abundance of Hole 68-502A.
62 records from (Table 4) Principal component analysis, paleotemperatures and distribution of infaunal benthic foraminifera in Late Quaternary sediments of ODP Hole 122-760A in the southeast Indian Ocean.
10 records from Oberservation of birds at station PS14/143 along 49° West.
1555 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México.
2560 records from Upper Silesian Museum, Bird Observations.
69 records from (Table 3) Relative percent abundance of planktic Foraminifera at DSDP Site 10-95, Paleocene.
1607 records from Données naturalistes de Quentin ROME.
223 records from Range table from benthic foraminifers in ODP Hole 171-1050A.
116 records from SEWBReC Springtails and allies (South East Wales).
424 records from (Table 5) Distribution of planktonic foraminifers in ODP Hole 112-683B.
2076 records from Planktic foraminifera assemblage in sediment core SO42-74KL.
361 records from Range table from benthic foraminifers in ODP Hole 172-1054B.
89 records from Nannofossil abundance of Hole 9-79.
97 records from BIRDRACE NABUhu Trier!.
108 records from Benthic foraminifera abundance in ODP Leg 155 holes.
9264 records from UK Biodiversity Action Plan Invertebrate Data for Wales.
609 records from Farmland bird database in Dumfries and Galloway, 1999-2011.
248 records from Plants galls.
1541 records from (Table T6) Calcareous nannofossil stratigraphy of ODP Hole 198-1210A.
130 records from Artenvielfalt auf dem Schulgelände.
1739 records from Range table from planktonic foraminifers in ODP Hole 157-953C.
174 records from Nannofossil abundance of Hole 64-479.
454 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core GIK12392-1.
149 records from Range table from planktonic foraminifers in ODP Hole 177-1089C.
7247 records from Dead benthic foraminifera in South Atlantic surface sediments.
238 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18.
69 records from BIRDRACE Pfeifenten.
1235 records from (Table T2) Benthic foraminfera stratigraphy of ODP Hole 199-1220B sediments.
15 records from Description of lithologic section units of IODP Hole 325-M0036A.
119 records from (Table 11) Dinoflagellate cyst species distribution in ODP Hole 112-687B.
288 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein.
615 records from DBRC Austropotamobius pallipes records 1960 - 2015.
8516 records from Données naturalistes de Bruno OGER.
1760 records from (Table 9) Planktonic foraminifera of late Quaternary sediments in DSDP Hole 41-368.
780 records from Distribution of agglutinated foraminifers in sediment core Well 6406/8-1.
66 records from Range table from benthic foraminifers in ODP Hole 139-855B.
267 records from Dierloch, nördlicher Mooswald (Freiburg-Hochdorf).
385 records from (Table 2d) Nannofossil distribution chart of petroleum well Great-Eastern-1.
274 records from BIRDRACE Asiola-Quartett.
6179 records from NE Scotland fish records 1800-2010.
69 records from Matter enrichment of the macrofauna community of MAC station 13077-001.
217 records from Birdrace-Ornis_im_Einsatz-Lahn-Dill-Kreis.
648 records from Range table from planktonic foraminifers in ODP Hole 155-930B.
624 records from (Table 2) Distribution of benthic foraminifera in the Cretaceous succession of DSDP Hole 95-612.
10 records from Données naturalistes d'Olivier BARDET.
958 records from Pollen profile ADR353.
97 records from Foraminifera species abundances from tow TT011_7-MOC66.
28 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2446-2.
5 records from Sächsische Schweiz (Pfaffenstein).
11944 records from Données ONEMA BDMAP 2014.
343 records from Conservación de la tortuga caguama del Pacífico (Caretta caretta): protección dentro del hábitat crítico de alimentación y desarrollo en Baja California Sur.
1171 records from Glasaalmigratie - Glass eel migration in the river Yser.
1026 records from (Appendix D) Analyses of the benthic foraminifer assemblage at ODP Hole 112-680B.
69 records from Naturpark Kottenforst-Ville 18.6.09.
10 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_1-CTD8.
54 records from Nannofossil abundance of Hole 7-64.
14 records from Kosrae Invasive Database.
45925 records from DDT05_2017_12_18.
510 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin.
1031 records from ConDidact Citizen Science Surveys - Spiders 2011.
83 records from Roter Berg Werdau (Leubnitz).
123 records from Planktic foraminifera abundance of Hole 36-329.
38 records from Abundance of benthos infauna at station POS128/2_276.
64 records from Mauernacker (Wettsaasen).
3755 records from Données naturalistes de Charlotte PICARD.
5 records from Ostracoda abundance of Hole 44-390.
98 records from Plasm bearing foraminifera counts of multinet M21/1_MSN615.
92 records from Wiesen in der Grünen Mitte.
285 records from Loup 2014 présence occasionnelle communale (réseau Loup-Lynx ONCFS).
112 records from Benthic foraminifera abundance of Hole 41-366.
76 records from Programme Ecoscope: données d'observations des écosystèmes marins exploités (Réunion).
165 records from Plasm bearing foraminifera counts from M35/1_MSN1048.
163 records from Dinoflagellate cysts of ODP Hole 189-1172D.
57 records from CSIRO Yellow Box Fragmentation Project.
673 records from Planktic foraminifera abundance of Hole 45-395.
23 records from Calcareous dinocysts in ODP Hole 80-550B, part 2.
14 records from Nannofossil abundance of Hole 3-18.
2 records from Données naturalistes (Rhopalocères et Zygènes) de Nicolas JEAN (données récoltées en tant que bénévole).
1921 records from Registros biológicos de predios promocionados como Reservas Naturales de la Sociedad Civil-RNSC en el Cañón de Amaime, municipio El Cerrito, Valle del Cauca, Colombia..
350 records from (Table T1) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1170D sediments.
114 records from BIRDRACE LiLaLau.
1348 records from Inventory of Wari maro forest (Benin).
27276 records from RECORD Odonata Data.
26 records from (Table T8) Occurrence of Neogloboquadrina pachyderma in ODP Hole 178-1098C.
137 records from SNH Invertebrate Site Condition Monitoring 2013/14: North Rothiemurchus Pinewood SSSI.
59 records from Schulteich Freie Waldorfschule Darmstadt.
72 records from Ostfriesland.
12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_4-CTD43.
4 records from Planktic foraminifera abundance of Hole 19-191A.
1331 records from (Table 2) Distribution of planktic foraminifers of sediment core D11957P.
1212 records from Freshwater fish records via iRecord.
91 records from Range table from planktonic foraminifers in ODP Hole 146-892A.
838 records from Phytoplankton abundance during Gunnar Thorson cruise GT90/5.
884 records from Diversité et distribution de quelques espèces de plantes agroforestières au Bénin.
171 records from (Table 3) Distribution of planktonic foraminifera in the larger size fraction of ODP Hole 120-749B.
567 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California.
690 records from Benthic foraminifera counts of sediment core GIK23352-3.
81 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach.
235 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido.
49 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, >125 µm fraction.
2512762 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014.
1426 records from (Table 5) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-682A, Part II.
28 records from Hainbachtal bei Oelsnitz / V..
77 records from Benthic foraminiferal assemblage (dead) in MUC SC1-K, size fraction 63-150 µm.
19 records from Small Cow-wheat distributions for Scotland 1999 to 2005.
164 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/014-6.
33 records from Waldstück am Schullandheim Bad Bederkesa.
297 records from Aves de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO.
15 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B2_818-16.
789 records from Assemblage of benthic foraminifera in sediment core GIK23414-8.
1 records from Données naturalistes d'Olivier DELZONS.
616 records from (Table AT6) Planktonic foraminiferal stratigraphy of ODP Hole 182-1130B.
218 records from (Table 2) Abundance of planktonic foraminifera in ODP Hole 113-689B, small size fraction.
68 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-11.
162 records from Schulhof Gymnasium Hürth Bonnstrasse.
174 records from BIRDRACE Bon(n)apartemöwen.
37 records from Canavans Ck realignment periphyton.
335 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó.
466 records from Benthic foraminifera counts of sediment core PS1852-2.
2606 records from Range table from planktonic foraminifers in ODP Hole 157-953A.
2 records from Zooplankton abundance measured on water bottle samples during Jan Mayen cruise JM6.
2106 records from (Table 17) Ranges of benthic foraminifers through the late Neogene in ODP Hole 115-713A.
20293 records from NatureShare.
141 records from Range table from planktonic foraminifers in ODP Hole 171-1052F.
145 records from Total foraminifera counts of multinet M21/1_MSN603.
180 records from Microzooplankton abundance measured on water bottle samples at station PS58/108-1.
19 records from Landesgartenschau.
22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz).
365 records from Nannofossil abundance of Hole 12-111A.
368 records from (Appendix I) Foraminifera abundance in DSDP Hole 7-62.
235 records from Planktonic foraminifer occurrences and zonations from IODP Hole 313-M0029A.
393 records from Heinersdorfer Sumpfwiese.
112881 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records.
18656 records from Arctic Species Trend Index (ASTI) : Marine.
114 records from UCM Vertebrate Observations Collection (Arctos).
53 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03.
3332 records from Dead benthic foraminifera of surface sediment of the Persian Gulf (Table 2).
538 records from Distribution of planktic foraminifera in surface sediments.
33416 records from Wolli Creek Preservation Society Bird Survey.
9603 records from Seabird Observations, Storm Bay, Tasmania, Australia, 1991-1994.
583 records from (Table S2) Relative abundance of coccolithophora in sapropel S1 of ODP Hole 160-964B, filtering preparation.
63 records from Inventaire des espèces végétales de la vallée de Gounti Yéna (Niamey).
274 records from Bernhardsthal.
125 records from Naturschutzgebiet Müchelholz (Mücheln).
163 records from Wiese am Waldrand (Gurtweil).
2006 records from (Table T4) Planktonic foraminiferal stratigraphy of ODP Hole 173-1069A sediments.
118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim.
11873 records from Midden-Limburg Fish Ponds Survey.
170 records from Range table from benthic foraminifers in ODP Hole 189-1171C.
240 records from Range table from benthic foraminifers in ODP Hole 198-1207A.
4 records from Distribution of meiobenthos in sediment core M23_123 (2) of the northeastern Atlantic (Table 1).
96 records from Redlisted beetles found in oak grove near Lake Østensjø.
825 records from (Table 4) Stratigraphic distribution of dinocyst taxa in ODP Hole 150-904A.
158 records from Planktic foraminifera counts at CTD station PS55/063.
2829 records from (Figure 3) Stratigraphic distribution of planktonic foraminifera in the Neogene of ODP Hole 122-761B.
3982 records from Leicestershire and Rutland Aculeate Records.
177 records from Range table from benthic foraminifers in ODP Hole 174-1072A.
179 records from Nannofossil abundance of Hole 24-232.
177 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c.
501 records from Range table from planktonic foraminifers in ODP Hole 155-932A.
54 records from Waldsee.
4373 records from Distribution des Cétacés et Siréniens dans les eaux de Nouvelle-Calédonie.
8352 records from Inventario florístico y entomofaunístico en tres objetos de conservación ecosistémicos en las zonas núcleo de las reservas estatales de Balam-kú y Balam-kin, Campeche.
41 records from Liether Park (LMS), 6c.
1340 records from Plasm bearing foraminifera counts during METEOR cruise M36/5.
13962 records from (Figure 3) Range chart of dinocysts of ODP Hole 104-643A.
26 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/041-2.
274330 records from Belgian IFBL Flora Checklists (1939-1971).
56 records from Plasm bearing foraminifera counts of multinet M12/3_MSN562.
729 records from Nannofossil abundance of Hole 30-288.
494 records from (Table 5) Distribution of calcareous nannofossil species at DSDP Hole 40-361.
1077 records from Planktic foraminiferal assemblages of the Paleocene-Eocene Thermal Maximum from ODP Hole 198-1210B, Shatsky Rise, Pacific Ocean.
312 records from Nannofossil abundance of Hole 36-329.
149 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction >150 µm.
104 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c.
115 records from Range table from planktonic foraminifers in ODP Hole 155-942C.
13 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_257-1.
2247405 records from Vascular plants in Denmark recorded under the The Nationwide Monitoring and Assessment Programme for the Aquatic and Terrestrial Environments (NOVANA).
63 records from Phytoplankton abundance in surface water in 2000, Ancon, Peru.
61 records from Total foraminifera counts from M35/1_MSN1063.
49 records from Nannofossil abundance of Hole 74-526.
127 records from Total foraminifera counts of multinet POS247/2_MSN1376.
256 records from (Table 4) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 129-801A.
53 records from Total foraminifera counts of multinet M21/5_MSN735.
531 records from (Appendix A2) Calcareous nannofossil counts of ODP Site 207-1260.
2808 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004.
22 records from Dinoflagellate abundance of Hole 14-144.
23 records from Range table from planktonic foraminifers in ODP Hole 144-874B.
26 records from Calcareous dinocysts in ODP Hole 80-550B, part 1.
237 records from Range table from benthic foraminifers in ODP Hole 161-974B.
69 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from POSEIDON cruise 334.
2845 records from Pat Livermore's Fungus Records 1976 - 2000.
192 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100320.
417 records from Pollen analysis of sediment profile TR0 from Truennensee.
21 records from Abundance of benthos infauna at station GIK23004-3.
208 records from Condamine Alliance.
3479 records from Relative abundances of dinoflagellate cysts in several IODP and DSDP holes.
181 records from Inventory of natural and agroforestry stands characterized by Xylopia aethiopica (Dunal) A. Rich. (south-Benin).
825 records from Small rodents in mountain birch forest 2002-2016.
4763 records from Sistema Arrecifal Veracruzano: condición actual y programa permanente de monitoreo: Primera Etapa.
139 records from (Table A.04) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (80-150 µm).
1 records from Conservación de la población de Loro Orejiamarillo (Ognorhynchus icterotis) en el piedemonte llanero, departamento del Meta.
682 records from St Andrews BioBlitz 2015.
19254 records from sarce_rockyshores.
1701 records from (Table 12B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-590B.
72 records from Plasm bearing foraminifera counts of multinet M21/1_MSN603.
171 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/587-16.
107 records from Faunal assemblage of sediment core TR149-31.
1626 records from Range table from planktonic foraminifers in ODP Hole 152-919A.
420 records from Phytoplankton abundance in surface water in October 1995, Ilo, Peru.
18 records from Naturtag.
926 records from Nannofossil abundance of Hole 94-610A.
14 records from Analyses of the recent components of sediment core PS1220-3.
59 records from Matter enrichment of the macrofauna community of MAC station 13368-008.
164952 records from Oiseaux nicheurs de France métropolitaine 2009-2012 - Nidification probable.
1124 records from Benthic foraminifera abundance of Hole 84-569, Part 1.
93 records from Plasm bearing foraminifera counts from M35/1_MSN1069.
204 records from Planktic foraminifera abundance of Hole 29-284A.
73 records from Planktic foraminifera abundance of Hole 49-409.
33 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, 30-63 µm fraction.
201 records from (Table Ib) Planktic foraminifera abundances in the earliest Paleocene sample interval of DSDP Hole 74-528 on the Walvish Ridge, South Atlantic.
1551 records from (Table 1) Range chart for planktonic foraminifers from ODP Hole 111-667A.
774 records from Biodiversidad ictica de la Isla Cayo Serranilla Expedición Seaflower 2017 proyecto Colombia BIO.
43 records from Total foraminifera counts from M35/1_MSN1045.
120 records from Total foraminifera counts of multinet M21/2_MSN650.
19 records from Equinodermos de las unidades ecológicas someras Expedición Seaflower Serranilla2017 - Proyecto Colombia BIO.
707 records from Planktic foraminifera abundance of Hole 49-408.
330 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE236.
3307 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments.
143 records from (Table 1.2.3.1) Abundance of sympagic meiofauna in the bottom-ice section of Polarstern cruise ANT-XXIII/7 sea-ice cores.
699 records from Foraminifera abundance of Hole 24-236.
87 records from Nannofossil abundance of Hole 10-91.
36 records from Range table from benthic foraminifers in ODP Hole 181-1119C.
3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-IR64.
66 records from (Table 9) Distribution of ostracode species in surface sediments of the southern Laptev Sea.
3402 records from (Table 2) Nannofossil occurrence in ODP Hole 101-627B.
662 records from Alterra (NL) - Microarthropods inventory in grassland and arable land.
482 records from Pez León en Venezuela.
1142 records from (Table 8) Distribution of planktonic foraminifera in the late Cretaceous and Eocene to early Miocene sections of ODP Hole 149-899B.
44 records from Planktic foraminifera abundance of Hole 51-417A.
238 records from Range table from benthic foraminifers in ODP Hole 181-1122C.
108 records from Total foraminifera counts of multinet M21/2_MSN628.
124 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/041-2.
77 records from Helechos del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO.
3718 records from (Table 3) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-502A from the Caribbean Sea.
287870 records from Florida Keys Reef Visual Census 2014.
16 records from Microzooplankton abundance and biomass at station NBP97-03-05-6.
28 records from Phytoplankton abundance at station Casma_2003-01-30_2, Casma, Peru.
96 records from Total foraminifera counts of trap L2_92_A43.
1338 records from Inventory of Bassila, Pénéssoulou, Wari maro, Djigbé, Lama and Bonou forests (Benin).
7 records from Nannofossil abundance of Hole 1-4.
654 records from Nannofossil abundance of Hole 21-205.
2550 records from (Table 1) Distribution of nannofossils in DSDP Hole 87-582B.
15 records from Analyses of the recent components of sediment core PS1403-1.
50 records from Coccolith counts of multinet SO119_MSN1288.
177 records from Spießwoogtal / Königsbruch (Fischbach).
158 records from Planktic foraminifera counts at CTD station M39/4_402CTD-55.
433 records from Nannofossil abundance of Hole 22-212.
306 records from Diversity, standing stock and distribution of living benthic foraminifera suborder groups (Table 3+5).
2351 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa.
46694 records from Records from the NIWA AllSeaBio marine biology database.
371 records from Inventario de Fauna Vertebrada de la Reserva Forestal Protectora Regional de los Cañones de los Ríos Melcocho y Santo Domingo.
2144 records from SPC CoFish Invertebrates Observations Marshall Islands 2007.
10110 records from Suivi Temporel des Libellules (STELI).
102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Akassine*.
16 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_2-CTD1.
1194909 records from First Bird Atlas.
2389 records from The Fish Sampling at Lata Fish Market in Temotu Province, Solomon Islands.
661 records from RV Investigator Voyage IN2017_V02 Seabird Observations, Australia (2017).
71 records from GPMM_Environnement_2017_12_18.
79 records from Sedimentological investigation on core V25-60.
7344 records from (Table 5) Distribution of calcareous nannofossils in ODP Hole 119-738C.
5 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0002A.
103 records from BIRDRACE Resopal-Darmstadt-Dieburg.
432 records from Abundance of large foraminifera in cores from transect HYD-02A, IODP Expedition 325.
15 records from Regenwasserabfangsbecken (Erlenbach).
6 records from Observation of birds at station PS14/152 along 49° West.
184 records from Range table from benthic foraminifers in ODP Hole 139-857C.
77 records from SNH Invertebrate Site Condition Monitoring 2015: Perchhall Loch SSSI.
10894 records from Occurrences of the invasive plant species Heracleum sosnowskyi Manden. in the Komi Republic territory (European North-East Russia).
156 records from Distribution of planktonic foraminifers in ODP Hole 104-642A (Table 2).
2807 records from Natura 2000 Vallée de la Seille.
591 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 2.
1025 records from Benthic foraminifera abundance of Hole 95-613.
388 records from Nannofossil abundance of Hole 4-30.
63085 records from Alien plant presence dataset from the point-radius plot surveys in 2010-2015 in Taiwan.
3 records from Microplankton counts and carbon biomass at station TT011_8-CTD96.
1704 records from Données naturalistes d'Anita GEORGES.
1995 records from Monitoreo y morfometría de la avifauna de la Universidad del Valle 2011-2012.
6 records from Ökosysteme rund um Wedel.
1187 records from (Table 15) Distribution of planktonic foraminifers in ODP Hole 108-666A.
67 records from Planktic foraminifera abundance of Hole 9-76.
1340 records from Nannofossil abundance of Hole 94-606.
186 records from Monitoring the dynamics of a medicinal tree species Haematostaphis barteri Hook. F. in Benin.
322 records from Triebesbach (Zeulenroda-Triebes).
76 records from BIRDRACE Nachtigallen.
68 records from Nannofossil abundance of Hole 24-233A.
2098 records from (Table 6) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-852B.
61 records from Données de Midi-Pyrénées transmises par Pascal Peyrache..
1284 records from ConDidact Citizen Science Surveys - Amphibians 2007.
88 records from Dinoflagellate abundance of Hole 28-274.
108796 records from Yorkshire Wildlife Trust - Non-sensitive records from all taxonomic groups.
4061 records from Restauración experimental de un popal invadido por el zacate alemán (Echinochloa pyramidalis, POACEAE) en el sitio Ramsar No. 1336 La Mancha y El Llano.
145 records from Abundance of radiolaria at station LV28-66-1.
358 records from Nannofossil abundance of Hole 85-574.
49 records from Total foraminifera counts of multinet FCA97C_MSN1345.
96 records from Données naturalistes (Rhopalocères et Zygènes) de Jude LOCK (indépendant).
1535 records from (Table 5) Distribution of planktonic foraminifera in the latest Pliocene to Holocene section of ODP Hole 149-898A.
119 records from Benthic foraminifera and algae abundance of Hole 81-552.
129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI.
96 records from Wiese und Weide am Waldrand von Gusterath.
30 records from Phytoplankton abundance at station Sechin_2003-12-17_2, Casma, Peru.
455 records from Unna-Mühlhausen, Wiesen.
376 records from Planktic foraminifera abundance of Hole 2-10.
564 records from IBF Monitoring of Plant Galls.
19 records from Données naturalistes de LE GLOANEC Vincent.
51807 records from Calf of Man (Isle of Man) Bird Observatory Daily Logs, 1959-64, 1974-5.
370 records from Size of planktic foraminifera at CTD station PS55/051.
10 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB01 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups.
1 records from Herpetofauna de la región El Huizache, San Luis Potosí.
38447 records from Leicestershire and Rutland Fungi and Lichen Records.
36 records from City of Edinburgh Natural Heritage Service - Large Red Damselfly Survey.
49 records from Abundance of living benthic foraminifera in sediment core CD86_06_BC5.
960 records from Range table from planktonic foraminifers in ODP Hole 144-873B.
308 records from Naturmiljø Bergensbanen 2015 (project number 616033).
22 records from Ostracoda abundance of Hole 24-238.
68 records from Coccolith counts of multinet SO119_MSN1281.
150090 records from Données BioObs - Base pour l’Inventaire des Observations Subaquatiques de la FFESSM.
15 records from Meiofauna abundance in sediment core 54301-010.
353 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo.
45918 records from Millipede (Diplopoda) records for Britain and Ireland to 2005.
60 records from Nannofossil abundance in sediment core PS1294-4.
96 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-94-GN3619940280200500.
477 records from Données naturalistes d'Aurélie CHEVILLON.
8848 records from NE Scotland other invertebrate records 1800-2010.
84 records from Range table from benthic foraminifers in ODP Hole 198-1213A.
152 records from (Table 7) Percent distribution of calcareous nannofossils at ODP Hole 125-786A.
259 records from Benthic foraminifera abundance of Hole 80-549A.
25 records from Base de données en ligne d'observations naturalistes de mammifères marins. www.faune-guyane.fr. GEPOG & LPO.
740 records from Vegetación de los remanentes de bosque andino, municipio de San Francisco (Cundinamarca).
99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz.
391 records from (Table 1) Absolute abundances of benthic foraminifera in ODP Site 120-747.
1544 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México.
347 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz).
25 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/088-4.
153 records from Nekton and plankton counts from bongo net (300, 500 µm) hauls of cruise GAE 1975/76.
34 records from Planktic foraminifera abundance of Hole 29-279.
1034 records from (Table 3) Distribution of Campanian-Maestrichtian calcareous foraminifers in DSDP Hole 78-543A.
567 records from Foraminifera abundance of Hole 74-526A.
272 records from Dinoflagellate abundance of Hole 81-555.
624 records from Dinoflagellate cysts of mooring MST-9 (station 915), full and empty cysts.
797 records from Relative abundance of Neogene nannofossils at ODP Site 165-998 from the Caribbean.
192 records from Range table from benthic foraminifers in ODP Hole 171-1049A.
1680 records from (Table 2) Oligocene to Pliocene nannofossil range chart for ODP Hole 134-828A.
2886 records from EDIT - ATBI in Gemer area (Slovakia).
88 records from Teich Berlin Wuhlheide.
186 records from Nannofossil abundance of Hole 27-259.
300 records from Ried und Sand - Artenvielfalt durch Beweidung.
112 records from Creag Riabhach Wind Farm: 2012-13 Ornithology and Protected Mammal Surveys.
1110 records from (Table 2) The presence and absence of whole and/or fragmented planktonic and benthic foraminifers at DSDP Hole 93-603.
148 records from AKG-Gelände (Bensheim).
237 records from Planktic foraminifera abundance of Hole 21-207.
12 records from Sarcodine counts and carbon biomass at station TT012_5-TM9.
16 records from (Tab. 9) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 17-166, Magellan Ridge, southwest of Hawaii.
54415 records from Cawthron Institute freshwater invertebrate data.
23 records from Benthic foraminifera abundance of Hole 93-603.
1460 records from Range table from benthic foraminifers in ODP Hole 151-909C.
629 records from (Tab. 8) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 27-261, Argo Abyssal Plain, northwest of West Australia.
18 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-13-4.
85 records from Ostracoda abundance of Hole 48-403.
348 records from Naturschutzgebiet Heiliger Hain (Wahrenholz).
390 records from Range table from planktonic foraminifers in ODP Hole 141-863A.
5662 records from Atomariine Beetle (Coleoptera) records for Britain and Ireland to 1992.
668 records from Walter Herwig 1978 (FFS): SeaStars (Echinodermata, Asteroidea).
226 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-959D.
80 records from Förderzentrum Schmölln.
20 records from Microzooplankton abundance and biomass at station NBP97-08-05-1.
728 records from Planktic foraminifera counts of sediment core V27-178.
209 records from Lebensraum Gesamtschule (Langerwehe).
425 records from Foraminifera abundance of Hole 64-481.
109 records from Benthic foraminifera abundance of Hole 56-436.
826 records from Coléoptères Silphidés du département du Loiret.
315 records from Size of planktic foraminifera at CTD station PS55/030.
7 records from Analyses of the recent components of sediment core PS1277-1.
584 records from Nannofossil abundance of Hole 60-458.
2177 records from Polychaetes in surface sediments off Sylt collected during HEINCKE cruise HE241.
158 records from Waldstück Bremerhagen LK Bio Kl. 12.
1097 records from Planktic foraminifera counts of sediment core RC08-49.
235 records from Estimación de la densidad poblacional y dieta del lince (Lynx rufus) Sierra Seri, Sonora y Janos, Chihuahua.
42 records from Meiofauna abundance in sediment core 13077-014.
509 records from Distribution of Cretaceous and early Danian planktonic foraminifera in ODP Hole 119-738C (Table 1).
4 records from (Table 1) PBDE and BDE congener concentration in adipose tissue of East Greenland polar bears collected 1999-2001.
541 records from Nannofossil abundance of Hole 78-542A.
561 records from Range table from benthic foraminifers in ODP Hole 146-889A.
120 records from Stable carbon and oxygen isotope ratios of calcareous dinoflagellate cysts and planktic foraminifera from the Campanian/Maastrichtian section of ODP Hole 113-690C in the Weddell Sea (Table 1).
371 records from Bannwald Burghauser Forst.
63 records from Données Cétacés Transmed.
9 records from Sarcodine counts and carbon biomass at station TT007_8-CTD99.
6117 records from Données des collections de cnidaires du MNHN.
565 records from Relative abundance of planktic foraminifera in sediment core RC17-69.
20452 records from SEWBReC Bees, Wasps and Ants (South East Wales).
12 records from Flora und Fauna am Mühlberg.
80 records from (Table 3) Relative abundances of palynoclasts, palynomorphs and microplankton in ODP Leg 112 samples.
530 records from Percentages of planktonic foraminifera species in sediment core V32-8.
20 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03.
5 records from Schulhof Montessori Schule (Rotenburg / Wümme).
69 records from Range table from planktonic foraminifers in ODP Hole 151-910A.
3976 records from Mise en place d'un suivi scientifique des odonates pour la production d’indicateurs de biodiversité.
89 records from Great British Bee Count 2016 - Stage 2 (records verified from photo).
111 records from Total foraminifera counts of multinet M33/1_MSN1029.
118 records from (Appendix A2) Cenomanian benthic foraminifera of ODP Site 207-1260.
832 records from Benthic foraminifera and algae abundance of Hole 81-552A.
12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_1-CTD1.
150 records from Monocotiledóneas del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017.
395 records from Planktic foraminifera abundance of Hole 32-310.
102 records from Birdrace-Die_Nachtraben-Stuttgart.
26 records from Dinoflagellate abundance of Hole 81-554.
174 records from Artenvielfalt des "Grünen Klassenzimmers".
42 records from Great British Bee Count 2015 - Stage 2 (records verified from photo).
194 records from Planktic foraminifera counts at CTD station M39/4_357CTD-15.
3753 records from Vascular plants of Amrum 2007-2008.
159 records from Total foraminifera counts of multinet M36/6_MSN1196.
26730 records from National Dormouse Database (NDD).
9 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016.
11 records from Ostracod species in Oligocene sediments of core CRP-3.
26 records from Nannofossil abundance of Hole 10-93.
2190 records from Modelos predictivos de distribución geográfica para Spizella wortheni, Cynomys mexicanus, Vulpes macrotis zinseri y Taxidea taxus berlandieri.
65 records from Planktic foraminifera counts of sediment core RC17-73.
12 records from Art´n Vielfalt im Kinderwald.
10 records from Analyses of the recent components in the sand fraction of sediment core PS1219-1.
5472 records from (Table 5) Eocene to Oligocene nannofossil range chart for ODP Hole 134-829A.
115 records from Succession of benthic hard-bottom communities abundance at Liliguapi, Paso Comau, Chile, in 2011.
251819 records from Phase 2 Lowland Grassland Survey of Wales.
385 records from Invasive Non-Native Species, Outer Hebrides.
16 records from Benthic macrofauna abundance of sediment core 13077-093.
1350 records from (Table 8B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 89-586B, Sections 5-2 through 8-4.
31 records from Phytoplankton abundance at station Casma_2003-01-07_1, Casma, Peru.
113 records from Abundance of radiolaria at station UT99-13-2.
65 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (79° N section).
1 records from Synthèse de la Répartition des populations de bouquetin des alpes en 2010 (réseau Ongulés sauvages ONCFS-FNC-FDC).
1420 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2010.
95 records from Birdrace-Buteo1_DO-Dortmund.
77 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM2.
480 records from (Table 2) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-679.
645 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE293.
1283950 records from Données issues de Clicnat (Base de données naturaliste picarde gérée par Picardie Nature).
296 records from DATABASE OF FINDS OF RARE LICHEN SPECIES Lobaria pulmonaria IN RUSSIA.
11320 records from SEWBReC Amphibians (South East Wales).
8 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station JULY-1994-D2.
2471 records from Données malacologiques des membres du Collectif GERMAIN.
9145 records from (Appendix 8) Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system.
372 records from Composición y estructura de la ornitofauna de la reserva de la biósfera Pantanos de Centla.
69 records from Schulgarten mit Klasse 8a (Essen).
7 records from Planktic foraminifera abundance of Hole 53-418B.
27 records from Benthic foraminifera abundance of Hole 34-320A.
445 records from Distribution of nanoplankton at trap WR2.
13624 records from Ecosphère_2017_12_18.
74 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea.
16 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT012_5-CTD45.
1607 records from Nannofossil abundance of Hole 86-577A.
98 records from Twite national sample survey in the UK in 1999.
4492 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas.
53 records from Nannofossil abundance of Hole 11-101A.
777 records from Isle of Wight non-native invasive species.
1489 records from Dinoflagellate cysts counts of sediment core MD95-2010.
581 records from Floristic records in the Moscow and Novgorod regions.
68 records from Total foraminifera counts of multinet M21/4_MSN701.
816 records from Espèces végetales sur sable roux du fourré de Ranobe, PK 32 Toliara.
9700 records from Lothian Wildlife Information Centre Secret Garden Survey.
882 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A.
4944 records from Données Ongulés et Lagomorphes en Bretagne de 2000 à 2016.
24 records from Nannofossil abundance of Hole 6-57B.
92 records from (Table 2) Ostracoda abundances in sediment core PS2185-6 (Lomonosov Ridge).
1673 records from Mayfly (Ephemeroptera) records from Britain and Ireland, via iRecord.
735 records from Range table from planktonic foraminifers in ODP Hole 155-938A.
81 records from Kystfuruskoger i Tysnes og Fusa.
91 records from Diatom abundance of Hole 95-613.
8 records from Die Bachspezies 2008/2009.
123 records from Birdrace-SportfreundeTriller-Münster.
3 records from Results of palynological analysis of Hole 302-M0004C.
45140 records from SIRFF - FNE Centre-Val de Loire - Données 2016.
68 records from Streuobstwiese.
802 records from Planktic foraminifera abundance of Hole 76-533.
23 records from Abundance of benthos infauna at station GIK23042-2.
10 records from Western Australian Museum provider for OZCAM.
1408 records from (Table 4) Distribution of Cretaceous calcareous nannofossils in ODP Hole 114-700B.
197 records from ABC_Event data recorded on a day trip to Mongolwe and Chikala Hills Forest Reserve, Machinga District.
123 records from Total foraminifera counts of multinet M21/2_MSN648.
285 records from NSG Hülenbuch Hörnle (Tieringen/Meßstetten).
2356 records from Distribution of living benthic foraminifera in surface sediments of the Norwegian Sea (Table 2).
3272 records from Mammifères marins Guadeloupe Antilles françaises (AET). Suppléments.
714 records from (Table 3) Nannofossil occurrence in the Albian of ODP Hole 101-635B.
118 records from Observation des insectes sur le territoire de la Métropole Rouen Normandie.
192 records from Alterra (NL) - Microarthropods inventory in Cranendonck area.
3 records from Tejidos colectados en la caracterización biótica para la conservación de especies amenazadas en el área de influencia del Oleoducto Bicentenario, departamentos de Arauca y Casanare, Colombia.
16 records from Hazel Dormouse in Ireland.
30 records from Nannofossil abundance in sediment core PS1313-4.
9 records from Nannofossil abundance of Hole 5-37.
113 records from (Table 4) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-706A.
51 records from Schulteich/Tümpel Thor-Heyerdahl-Gymnasium (Kiel).
285 records from Range table from planktonic foraminifers in ODP Hole 171-1053A.
2 records from The Fungal Collection at the Botanische Staatssammlung München.
123 records from Total foraminifera counts of multinet M21/4_MSN694.
399 records from Planktic foraminifera abundance of Hole 14-142.
39326 records from Insects, Outer Hebrides.
2 records from Distribution of Quinqueloculina sp. in sediment core 12930-014.
46 records from An der Ohm, (Wettsaasen).
95 records from Foraminifera species abundances from tow TT011_6-MOC65.
51 records from Phytoplankton abundance at station Rigel_4_2005-08 in August 2005, Chipana, Chile.
149 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas.
112 records from Nannofossil abundance of Hole 73-521A.
7 records from Analyses of the recent components in the sand fraction of sediment core PS1276-1.
6 records from Anfibios y reptiles del municipio de Cuetzalan del Progreso, Puebla.
3 records from Range table from planktonic foraminifers in ODP Hole 169-1038E.
3132 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha).
969 records from Gurgltal (Tarrenz).
91 records from Radiolaria assemblage in sediment core GIK23400-3.
20 records from Riedkanal Bötzingen.
39 records from Nannofossil abundance of Hole 37-333A.
27 records from Planktic foraminifera abundance of Hole 27-259.
2423 records from SSNATV_2017_12_18.
20 records from Planktic foraminifera abundance of Hole 19-185.
64 records from (Table T10) Calcareous nannofossil stratigraphy of ODP Hole 198-1212A.
1019802 records from Dragonfly records from the British Dragonfly Society's Dragonfly Recording Network for the period up to 2014.
95 records from Überschwemmungsgebiet der Wied.
467 records from Données naturalistes (Rhopalocères et Zygènes) de Benoit DUHAZÉ (CEN Aquitaine).
318 records from Size of planktic foraminifera at CTD station PS55/018.
413 records from Phytoplankton abundance during Lev Titov cruise LT91.
20 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_276-1.
50 records from Inventario de vertebrados nativos en las islas Guadalupe, San Benito, Natividad, Asunción, San Roque, Isabel, Marietas, Socorro, Banco Chinchorro y Arrecife Alacranes.
90 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1378.
35 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/091-4.
193 records from Planktic foraminifera abundance of Hole 94-610.
7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa)..
523 records from Percentages of planktonic foraminifera species in sediment core V30-49.
69 records from (Table 5) Abundance of selected helicoliths at DSDP Site 82-563 in the North Atlantic.
4 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR50.
42 records from (Table 2) Major nannofossil abundances in three Leg 194 site survey gravity cores.
4 records from Analyses of the recent components of sediment core PS1275-1.
89 records from Birdrace-Team_Wangerooge-Friesland.
11 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/313-1.
1452 records from (Table 4) Distribution of Pleistocene to early Pliocene nannofossils in ODP Hole 108-658A.
264 records from (Table 4) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-847B.
478927 records from KTP Ring Data.
49 records from Données naturalistes (Rhopalocères et Zygènes) de Bob WHITMARSH (indépendant).
8 records from Microzooplankton abundance and biomass at station TT050_24-12.
11389 records from Dragonfly (Odonata) species records up to 1997 held by Leicestershire Environmental Resources Centre.
152 records from Composition of the fine silt fraction in surface sediments of the northwest African continental margin (Appendix Tab. 4).
35 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 63-125 µm fraction.
107 records from Microzooplankton abundance measured on water bottle samples at station PS65/580-2.
80 records from Range table from planktonic foraminifers in ODP Hole 139-855A.
247 records from Abundance of large foraminifera in cores from transect NOG-01B, IODP Expedition 325.
126 records from Total foraminifera counts of multinet M21/2_MSN651.
2136 records from (Table 1) Relative abundance of planktic foraminifera in Maastrichtian sediments of DSDP Hole 74-525A from the Walvis Ridge, South Atlantic Ocean.
75 records from Plasm bearing foraminifera counts of multinet M21/5_MSN730.
9 records from Benthic macrofauna abundance of sediment core 12930-048.
9832 records from Evaluation de la dynamique de la flore aquatique au Bénin en association avec les espèces envahissantes Pistia stratioides et Eichhornia crassipes. Data mobilized in the framework of JRS Biodiversity Foundation funded project.
98 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1381.
666 records from Macroinvertebrate abundance in montane tropical streams of varying land-use, Ecuador.
53 records from Bad Bodenteicher Heide.
3 records from ALERT Non-Native Species Records for Signal Crayfish.
96 records from Nannofossil abundance of Hole 38-336.
12 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_11-CTD132.
88 records from Ober-Olmer Wald 09.
536 records from Planktic foraminifera abundance of Hole 14-141.
1 records from Distribution of Quinqueloculina sp. in sediment core 13200-045.
1032 records from Étude entomologique des forêts publiques de Martinique, pour l'ONF.
48 records from Content of coarse fraction and G. menardii in sediment corev V25-44.
39 records from Inventaire des oiseaux sur le territoire de la métropole Rouen Normandie.
2673 records from PondNet data 2012-2014.
276 records from (Table 6) Ranges of benthic foraminifers through the Oligocene in DSDP Hole 22-216.
44 records from Planktic foraminifera abundance of Hole 63-472.
1609 records from Derbyshire Casual LEPIDOPTERA records - Casual records collated by Derby Museum..
675 records from (Tab. 3) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 11-100, Cat Gap Area, western Atlantic Ocean.
27 records from Phragma-Thermis/Thessaloniki.
2822 records from Finnish monitoring scheme of birds and mammals visiting bird feeders during winter.
1 records from Données naturalistes de Frédéric JARRY.
13014 records from Données de l'atlas des Mammifères sauvages de Midi-Pyrénées (données agrégées à la maille de 10km).
2856 records from Alien macro-invertebrates in Flanders, Belgium.
2554 records from Black grouse annual lek surveys in Dumfries and Galloway, 1980-2011.
345 records from (Table 3) Relative abundance of selected benthic foraminifera in ODP Hole 104-642C.
560 records from Planktic foraminifera abundance of Hole 15-149.
3939 records from Census of plant species in Pahou forest reserve.
15 records from Naturschutzgebiet Ahrschleife (Altenahr).
3888 records from (Figure 3) Stratigraphic ranges of selected planktonic foraminifers at ODP Hole 101-626C.
299 records from Situación actual de ocho especies de anfibios en categoría de riesgo en Veracruz.
368 records from Lillachtal mit Kalktuffquelle bei Weißenohe.
69 records from Nannofossil abundance of Hole 3-15.
15 records from Lepidurus arcticus survey Northeast Greenland 2013.
151 records from VSN-Wiese.
180 records from Planktic foraminifera of surface sediments off Portugal and Morocco (Table 4).
120 records from Planktic foraminifera counts at CTD station M39/4_366CTD-22.
966 records from Live benthic foraminifera of surface sediments from the East Atlantic continental margin off Portugal (Table Tab. 4, 6).
631 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 149-898A.
54 records from Données naturalistes d'Amélie TINAT.
233 records from Umgebung der Gesamtschule Winterhude (Hamburg).
68 records from Range table from planktonic foraminifers in ODP Hole 178-1096B.
190 records from Relative abundance of ostracods in sediment core Sv09.
2009 records from Local BioBlitz Challenge 2013.
209 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/009-6.
701 records from Range table from benthic foraminifers in ODP Hole 151-913B.
216 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru.
73 records from Rhopalocères du PNR Périgord Limousin au 15/10/2015.
1797 records from Phytoplankton abundance during Arnold Veimer cruise AV90/2.
1985 records from (Table 16) Distribution of planktonic foraminifera in the late Paleocene to earliest Oligocene section of ODP Hole 149-900A.
124 records from Kirkliston Range stream monitoring.
12 records from Naturschutzgebiet Swistbachaue (Eckendorf).
2394 records from (Table 1) Range chart of calcareous nannofossils in ODP Hole 122-761B.
14210 records from WDC Shorewatch Sightings.
28435 records from Diversidade e ocorrência de peixes do lago Niassa (2006-2018).
27308 records from Occurrence d'ongulés et Lagomorphes de Bourgogne synthétisées par la Société d'histoire naturelle et des amis du muséum d'Autun (SHNA).
12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_7-CTD84.
19 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, 63-150 µm.
66 records from Foraminifera abundance of Hole 55-432A.
869 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru.
1536 records from Whale catches in the Southern Ocean.
16 records from Benthic macrofauna abundance of sediment core 13200-008.
12 records from (Table T6) Relative abundance of Cretaceous plant microfossil taxa of ODP Site 188-1166.
31014 records from River Biologists' Database (EPA).
49805 records from CABI Africa Invasive and Alien Species data.
7469 records from Eurobodalla Regional Botanic Gardens.
1521 records from (Table T1) Nannofossil abundance of volcaniclastic and other lithologies from ODP Hole 197-1203A.
55 records from Great Eastern Ranges - Slopes to Summit.
133 records from Total foraminifera counts of multinet M10/2_MSN319.
79 records from Phytoplankton abundance at station Rigel_1_2005-02 in Febraury 2005, Chipana, Chile.
8141 records from Tiroler Landesmuseum Ferdinandeum.
67 records from Tongrube bei Hettstedt.
4 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO.
104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV).
180 records from Total foraminifera counts of multinet M21/1_MSN605.
9190 records from Weddell Seal census, Vestfold Hills, Antarctica.
8851 records from Odonata records from RSPB Reserves 1970-2009.
16098 records from The BCT/MTUK Bats & Roadside Mammals Survey.
1031 records from Données supplémentaires Atlas des Mammifères marins.
85 records from Plasm bearing foraminifera counts from multinet SO119_MSN1295.
130 records from Abundance of dead benthic foraminifera in sediment core CD86_02_BC5.
79717 records from CSIRO, Soviet Fishery Data, Australia, 1965-1978.
11 records from Planktic foraminifera abundance of Hole 2-9.
1681960 records from NBIS Records to December 2016.
149 records from Abundance of radiolaria at station UT99-23-2.
12594 records from Inventario avifaunístico de las áreas focales Zoh-Laguna y La Montaña en el corredor biológico mesoamericano Sian Ka'an- Calakmul, México.
27 records from Planktic foraminifera abundance of Hole 51-417B.
1460 records from Census of invasive alien plant species of Benin (West Africa) by SOS Biodiversity.
305 records from Rohrmeistereiplateau und angrenzendes Gebiet.
1426 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004.
49 records from Distribución, abundancia y selección de hábitat de especies de aves amenazadas y en peligro de extinción en los bosques de montaña de Chiapas.
2 records from Planktic foraminifera abundance of Hole 28-267.
2676 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data.
375 records from (Appendix E) Stable carbon and oxygen isotope composition of Globigerinoides sacculifera of ODP Hole 121-758B.
2859 records from Planktic foraminifera abundance in counts of Hole PRAD1-2.
77 records from Distribution of planktonic foraminifera of sediment core SH1972_1.
706 records from South American Antarctic Marine Biodiversity Literature.
103 records from Métropole_Nice_Côte_d'Azur_2017_12_18.
398 records from (Table 5) Range chart of benthic and planktonic foraminifera of ODP Site 127-797.
47 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1384.
3253 records from Hemiptera: Auchenorrhyncha: Records for Kent.
16744 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture.
5856 records from (Table T1) Calcareous nannofossil stratigraphy of ODP Site 198-1213.
5538 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B.
1051 records from BOEM Beaufort Sea, Alaska, Fish and Invertebrate Haul and Catch, with Oceanography, 2008.
94 records from Distribution of planktonic foraminifera of sediment core SH1972_3.
2538 records from (Figure 5) Distribution of benthic foraminifers in the upper Eocene, Oligocene, and Quaternary of DSDP Hole 71-511.
88 records from Total foraminifera counts from M35/1_MSN1065.
2167 records from Marine Turtles.
196 records from Foraminifera abundance of Hole 33-317A.
2 records from Microzooplankton abundance and biomass at station TT050_26-18.
18818 records from Flora d'Andorra.
22 records from (Table 3) Foraminiferal species in DSDP Sample 78-541-5-3,19-21.
8 records from Microzooplankton abundance and biomass at station TT054_21-14.
1048 records from Données "faune" de l'AVEN du Grand-Voyeux pour le SINP île de France.
120 records from Total foraminifera counts of multinet M21/2_MSN650.
44 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB04 in the euphotic zone of the Aegean Sea in March 1998. Part 2 - dinoflagellates.
6 records from Microzooplankton abundance and biomass at station NBP97-03-03-5.
502 records from Concentration of siliceous microplankton in surface sediments, size fraction > 40 µm.
239 records from Nannofossil abundance of Hole 8-73.
210 records from Nannofossil abundance of Hole 67-499B.
10 records from Sediment properties of core PLG95B_06BOXG.
904 records from Thibaut_LACOMBE_2017_12_18.
78830 records from Standing Waters Database - Scotland.
58 records from Abundance of living benthic foraminifera in sediment core CD86_08_BC5.
262 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB01 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates.
2205 records from (Table 2) Distribution of calcareous nannofossils in ODP Hole 119-738C.
20 records from (Table 1) Occurrences of ostracodes in ODP Hole 122-761B.
54 records from Plasm bearing foraminifera counts of multinet M21/2_MSN629.
48 records from Junge Heide, Radebeul/Dresden.
178 records from Re-examination of the reef corals of Cocos (Keeling) Atoll, Charlie Veron.
99 records from Naturgrundstück (Eutin).
4545 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene of ODP Hole 105-645E (Table 1).
16 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 191-1179C.
8677 records from Bird Records held by Greater Manchester Ecology Unit.
6410 records from Records from the RHS insect reference collection.
265 records from Les mollusques terrestres de la faune de Corse : Mission 1996 de Theo RIPKEN. Muséum national d'Histoire naturelle, Paris et DIREN Corse.
68663 records from Données de l'Observatoire de la Faune de Bourgogne.
1168 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588.
170 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-17.
187 records from Nannofossil abundance of Hole 9-77B.
243 records from (Table 2) Occurrence and estimated abundance of planktonic foraminifers at DSDP Hole 85-571.
7 records from Range table from benthic foraminifers in ODP Hole 178-1096A.
20 records from Données naturalistes de Jean-Patrick Le Duc.
18 records from Sarcodine counts and carbon biomass at station TT012_5-PMOC5.
10 records from Planktic foraminifera abundance of Hole 6-47A.
350 records from (Table 2b) Nannofossil distribution chart of ODP Hole 122-761B.
3668 records from ARKO strandeng.
837 records from Range table from benthic foraminifers in ODP Hole 172-1063A.
322 records from Nannofossil abundance of Hole 49-408.
140 records from (Table 2) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-597.
11 records from Analyses of the recent components of sediment core PS1011-1.
87 records from Nannofossil abundance of Hole 11-106.
368 records from Biological Recording in Scotland - Bumblebee Survey.
8 records from Description of lithologic section units of IODP Hole 325-M0049B.
21 records from MVZ Herp Observations (Arctos).
245 records from Herrensee-Gebiet (Fischbachtal im Odenwald).
324 records from Parc_Naturel_Régional_des_Préalpes_d'Azur_2017_12_18.
60 records from Amtsrain Apolda-Zottelstedt.
75 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM1.
245 records from (Table 9) Relative abundance of calcareous nannofossil species across the Cretaceous/Paleocene boundary at ODP Hole 120-750A.
143 records from Planktic foraminifera abundance of Hole 18-179.
58 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB03 in the euphotic zone of the Aegean Sea in March 1998. Part 2 - dinoflagellates.
117 records from GEO-Hauptveranstaltung Bodden (Vilm).
3312 records from (Appendix A) Campanian-Maastrichtian calcareous nannofossils in DSDP Hole 44-390A.
31 records from Coccolith counts of multinet M32/5_MSN974.
230 records from (Table 2) Range chart for planktonic foraminifers from ODP Hole 111-677B.
13 records from Meiofauna abundance in sediment core 54301-009.
120 records from Nannofossil abundance of Hole 31-299.
225 records from (Table 2) Components of turbidite samples of ODP Leg 101 holes.
9476 records from (Table 1) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-871A.
2307 records from Nekton and plankton counts from RMT (4500 µm) hauls of cruise GAE 1975/76.
518334 records from RECORD Vascular Plant Data.
735 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during Friedrich Heincke cruise FHE238.
227 records from Benthic meiofauna abundance in surface sediment of core PLG93_BCORE2.
2045 records from Mollusc (non-marine) data for the Channel Islands.
78 records from Total foraminifera counts of multinet M21/4_MSN695.
390 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206.
97 records from Dorfrand Mauderode.
61 records from Shrews of Poland.
152 records from (Table 2) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-543.
3430 records from NDFF Wall Plants Monitoring Program.
9 records from Nannofossil abundance of Hole 2-11.
24 records from (Table 1) Analyses of coarse fraction of DSDP Hole 94-609.
19 records from Meiofauna abundance in sediment core 12930-075.
28711 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine.
30 records from Nannofossil abundance of Hole 6-48B.
561 records from (Table 7) Species composition of clusters, ODP Holes 139-856A and 139-857A.
181715 records from Marine benthic dataset (version 1) commissioned by UKOOA.
58 records from Nannofossil abundance of Hole 3-20C.
292 records from Occurence of marine palynomorphs of sediment core CRP-1 (Table 1).
4 records from Abundance of microplankton from bottle APRIL-2000-K3.
81 records from Range table from planktonic foraminifers in ODP Hole 177-1089D.
129 records from Total foraminifera counts of multinet POS247/2_MSN1383.
1438 records from Inventaire des Crustacés Décapodes de France métropolitaine. Données du compte CardObs 1113.
63 records from (Table 11) Planktonic foraminifer abundance of ODP Hole 162-987A.
2209 records from Planktic foraminifera abundance in per cent of Hole PRAD1-2.
42 records from Abundance of three benthic foraminifera species in surface sediments of a North-eastern Atlantic Abyssal Locality.
4 records from Planktic foraminifera abundance of Hole 23-223.
931 records from Données naturalistes de Mathilde DUSACQ.
1024 records from BUND - Dassower See (Lübeck/Dassow).
346 records from Birds and plant species near Petushki town (Vladimir region).
81 records from Donación de la base de datos resultado del diagnóstico de la diversidad de maíces nativos, su agroecosistema y sus parientes silvestres presentes en Papigochic y su zona de influencia..
984 records from Phytoplankton abundance in surface water in September 1997, Chimbote, Peru.
4 records from Sächsische Schweiz (Wehlener Gebiet).
68663 records from Données de l'Observatoire de la Faune de Bourgogne.
188 records from Nematode abundance of the Eastern Mediterranean Sea in cold seep sediments collected during Maria S. Merain cruises MSM13/3 and MSM13/4 in 2009.
29 records from Nannofossil abundance of Hole 9-81.
113 records from Appendicularia abundance of station M9_A near the Great Meteor Bank, Northeast Atlantic (Table 1).
2588 records from ConDidact Citizen Science Surveys - Spiders 2014.
363 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008.
6067 records from Arthur Chapman Observations.
570 records from Cuxhavener Küstenheiden.
106 records from vegoek.
40 records from Planktic foraminifera abundance of Hole 14-137.
356 records from Dinoflagellate abundance of Hole 94-607.
1105114 records from Hatikka Observation Database.
65 records from Phytoplankton abundance at station Sechin_2003-07-15_1, Casma, Peru.
3714 records from Fungi and Lichens, Outer Hebrides.
344 records from (Table T3) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones P5-P6b.
520 records from Planktic foraminifera counts of sediment core V22-196.
1 records from Synthèse de la Répartition des populations de cerf élaphe en 2000 (réseau Ongulés sauvages ONCFS-FNC-FDC).
11 records from Données d'observation opportunistes collectées durant la campagne de prélèvements sédimentaires SHELL/CREOCEAN en Guyane française en 2013. Shell Exploration and Production France.
1422 records from Australian Institute of Marine Science (AIMS) - Lizard Island Reef Biodiversity Expedition, Queensland, Australia (2008 - 2009).
588 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A.
23 records from Morphologische Daten von Natrix.
7 records from Abundance of nematoda in sediment profile M3/1_012 from the Iberian deep sea basin (Table 5).
63 records from Range table from planktonic foraminifers in ODP Hole 139-858A.
1703 records from (Table 3) Ranges of benthic foraminifers from the late Eocene through the Oligocene in ODP Hole 115-707A.
292 records from Planktic foraminifera abundance of Hole 9-82.
738 records from Nannofossil abundance of Hole 30-287.
598 records from Caracterización biológica de la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia.
455 records from GERECO_Environnement_2017_12_18.
208 records from (Table 4) Distribution of recurrent benthic foraminifera at DSDP Hole 75-530A, from Campanian and Maestrichtian.
53 records from Schulgarten Fichteschule.
95 records from BIRDRACE accipiter hardcore birding.
20 records from Meiofauna abundance in sediment core 13077-021.
890 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE262.
229 records from Distribución y estructura poblacional de la tortuga de Berlandier, (Gopherus [=Xerobates] berlandieri) en México.
86 records from Fliegenhaupt Marksuhl.
56 records from Planktic foraminifera abundance of Hole 23-227.
2199 records from Back from the Brink vascular plant species abundance and distribution for Great Britain for the period 2002-2009.
41 records from Newhaven Sanctuary observations.
226 records from (Table 2) Stable oxygen and carbon data, and relative abundances of selected planktonic foraminiferal species in the surface sediment samples retrieved during the SO-189 cruise off W Sumatra.
881 records from Relative abundance of adult opstracoda shells of surface sediment samples from the Persian Gulf (Table 1b).
1028 records from IBF Monitoring of Fungi.
2242 records from (Table 3) Distribution of planktonic foraminifera in the early Cretaceous and early Eocene to late Oligocene sections of ODP Hole 149-897C.
27 records from Benthic foraminifera and algae abundance of Hole 81-553.
883 records from Nannofossil abundance of Hole 15-154A.
43 records from Macrofauna abundance in surface sediment sampled during cruise DI237.
119 records from Programme de valorisation des zones humides chassées - volet Amphibiens.
2560 records from Caracterización de flora, edafofauna epígea, anfibios y aves del Complejo de Páramos Pisba, Boyacá.
100 records from (Figure 5) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 103-640A.
25 records from Antarctic Krill occurrence data from Spanish RV "Fruela".
9275 records from Données de la collection d'ichtyologie du MNHN (GICIM).
135 records from Total foraminifera counts of multinet M12/3_MSN558.
53 records from Données 2017 de l'Observatoire de la Biodiversité des Forêts.
236 records from Knechtweide (Kohlfurth).
245 records from données naturalistes de ALZIAR Gabriel.
18 records from Benthic macrofauna abundance of sediment core 12930-073.
23 records from (Table 4) Relative abundance of the major nannofossil groups in the Lower Cretaceous of ODP Hole 113-693A.
25 records from Range table from planktonic foraminifers in ODP Hole 192-1187A.
1110 records from (Table 8) Distribution of Pleistocene to early Pliocene nannofossils in ODP Hole 108-662A.
454 records from Inventario herpetofaunístico del valle semiárido de Tehuacán-Cuicatlán.
582 records from Stable isotope data and sedimentology of core SO42-74KL.
83 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-94-GN3619940280200800.
83 records from Meniscus Midges (Dixidae) of Ireland.
117 records from Total foraminifera counts of multinet POS247/2_MSN1382.
279 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/591-11.
139 records from Mosquitoes (Culicidae) of Ireland.
233 records from Nekton and plankton counts from Wechselnetz-Hai (300 µm) hauls of cruise GAE 1975/76.
1498 records from Amphibians and reptiles of Ireland.
224 records from Natura 2000 PnrL.
23 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB03 in the euphotic zone of the Aegean Sea in March 1998. Part 1 - diatoms.
936 records from (Figure 3) Distribution chart of dinoflagellate cysts of Cretaceous age from ODP Hole 103-638B.
206 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/041-2.
144 records from BIRDRACE Punkbirder Helgoland.
339 records from Phytoplankton abundance measured on water bottle samples at station PS65/508-2.
53 records from (Table 2) Benthic foraminifers at DSDP Hole 72-515A.
89596 records from Wicken Fen nature reserve species data held by The National Trust.
288 records from Planktic foraminifera counts at CTD station M39/4_352CTD-11.
456 records from Range table from benthic foraminifers in ODP Hole 172-1057B.
50 records from Phytoplankton abundance at station Sechin_2003-12-28_2, Casma, Peru.
483 records from SEWBReC Lacewings and Allies (South East Wales).
318 records from Nannofossil abundance of Hole 4-29.
38 records from Foraminifera species abundances from tow TT011_3-MOC60.
1511 records from Helmintos parásitos de peces del sureste de México.
61 records from Naturpark Kottenforst-Ville 15.6.09.
418 records from Radiolaria assemblage in sediment core GIK23259-2.
268 records from Range table from benthic foraminifers in ODP Hole 159-959A.
246 records from Araignées PNRL-2010 (Troyon,Jezainville-pelouse, Genicourt-pelouse).
1134 records from Alterra (NL) - Microarthropods inventory in European countries.
4 records from Range table from benthic foraminifers in ODP Hole 194-1193A.
63 records from Total foraminifera counts of multinet M21/4_MSN706.
294 records from Distribution of calcareous foraminifers in sediment core Well 6407/9-3.
173 records from FFH-Gebiet Klosterwasser/Burkau.
17 records from Assemblage of living benthic foraminifera in sediment core CD146_55918#7, >150 µm.
353 records from Données naturalistes de Hubert GUIMIER.
2646 records from (Table 3) Stratigraphic distribution of dinocyst taxa in ODP Hole 150-903C.
1726 records from Collection rousset -1947-2013.
1860 records from Données naturalistes de Hervé BOUYON.
399 records from (Table 2) Distribution of recurrent planktonic foraminifera at DSDP Hole 75-530A.
152 records from Wildkräuter.
255 records from Données naturalistes de BALLUCK Cindy.
2 records from Microzooplankton abundance and biomass at station TT050_2-10.
108 records from Total foraminifera counts of multinet M21/2_MSN629.
96 records from Plasm bearing foraminifera counts of multinet M21/2_MSN650.
154 records from Planktic foraminifera assemblage in sediment core GIK23065-2.
590 records from Foraminifera and stable isotopes of sediment core PS1754-1.
82 records from Total foraminifera counts of multinet M12/3_MSN560.
152 records from Total foraminifera counts of multinet POS247/2_MSN1372.
2 records from Dinoflagellate abundance of Hole 85-572C.
47 records from Microplankton abundance at Station MARCH-1998-GN36199804610MSB01 in the euphotic zone of the Aegean Sea in March 1998. Part 1 - diatoms.
48 records from Artenerfassung für Jedermann in der Grundschule Kirchboitzen.
270 records from Registros biológicos de aves Distrito de Manejo Integrado Musichi y Santuario de Fauna y Flora los Flamencos, La Guajira..
755 records from Freiburger GEO-Tag der Artenvielfalt.
9054 records from Highland bird data 2002 - 2003 - non-breeding records.
18 records from (Tab. 14) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 32-307, Hawaiian Magnetic Lineations.
197 records from Tortue Olivâtre. Données publiées dans le cadre du projet JRS Bénin.
8 records from Abundance and carbon biomass of phytoplankton at station TT008_5-CTD50.
130 records from ABC_Ndangopuma_hills_eventdata_25_11_2005.
99 records from Total foraminifera counts from M35/1_MSN1061.
6 records from Inventaire de la flore des espaces verts de la CREA avec le protocole Florilèges.
88 records from Plasm bearing foraminifera counts of multinet M21/2_MSN627.
18 records from Range table from planktonic foraminifers in ODP Hole 182-1129B.
4158 records from RNF - Données du Parc Naturel Régional du Vercors.
8 records from Range table from planktonic foraminifers in ODP Hole 171-1049B.
1941 records from (Table 19) Ranges of benthic foraminifers from the late Neogene through the Pleistocene in ODP Hole 115-707A.
1910 records from RECORD Freshwater Fish Data.
1831 records from Insectes Hyménoptères Scollidés de France.
19 records from Microplankton data off Chipana Bay, 2006, Chile.
18 records from GEO-Tag der Artenvielfalt der Klasse 7c am Gymnasium Allee im Wohlers Park.
1555 records from (Table 2) Relative abundances of benthic foraminifera in ODP Hole 128-798B.
4717 records from Weddell Sea macrozoobenthos EASIZ I.
320 records from Counts of benthos communities in Kongsfjorden in 2009.
1345 records from Distribution of planktic foraminifera in sediment core GIK23415-9.
603 records from IOW Natural History & Archaeological Society Marine Records.
5359 records from Fauna y flora en áreas con cultivos de palma de aceite en el norte y oriente de Colombia.
12 records from Données naturalistes de Piotr DASZKIEWICZ.
1 records from Microplankton counts and carbon biomass at station TT008_4-TM3.
12 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_10-CTD124.
2528 records from Communauté_de_communes_Asse_Bléone_Verdon_2017_12_18.
361 records from Phytoplankton abundance measured on water bottle samples at station PS65/545-1.
145 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/092-3.
67 records from Range table from planktonic foraminifers in ODP Hole 141-861A.
4889 records from Base de datos de la distribución de la flora de la Reserva de la Biosfera Tehuacán-Cuicatlán.
135 records from Waldi-Weiher.
175 records from Total foraminifera counts of multinet SO118_MSN1252.
8 records from Analyses of the recent components of sediment core PS1278-1.
210 records from (Table 1) Distribution of foraminifera in the Miocene section of ODP Hole 133-815A.
459 records from Gewann Krampf (Heilbronn).
18 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-960A.
74 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle.
65 records from Nannofossil abundance of Hole 24-234.
49 records from Smear slide analysis on sediment core GeoB4212-2.
1 records from Synthèse de la Répartition des populations de cerf élaphe en 1988 (réseau Ongulés sauvages ONCFS-FNC-FDC).
17 records from Benthic macrofauna abundance of sediment core 13201-002.
52 records from Biología reproductiva de Hechtia schottii Baker ex Hemsley (Bromeliaceae), una especie dioica y rara de la Península de Yucatán.
64 records from Distribution of less-numerous macro-endofauna in surface sediments at Fladen Ground stations, North Sea (Table 4).
80 records from (Table 2) Relative abundances of shallow-water foraminifera in ODP Hole 133-821A.
30 records from Planktic foraminifera abundance of Hole 14-144.
1 records from Microplankton counts and carbon biomass at station TT011_9-CTD115.
192 records from Inventaire des Spongiaires des eaux peu profondes de la zone maritime du Parc National de la Guadeloupe (PNG).
800 records from (Table 9) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-711A.
2436 records from Diet results from Adelie penguins at Bechervaise Island and Whitney Point, 2012/13.
156 records from SNH Invertebrate Site Condition Monitoring 2013/14: Earlshall Muir SSSI.
12 records from Nano and microzooplankton abundance and biomass at station NBP97-01-01-10.
157 records from Planktic foraminifera counts at CTD station PS55/078-1.
355 records from (Table 2) Species density and composition of an inshore and offshore station in Kongsfjord, Svalbard.
4 records from Determinación de la clase Reptilia presente en el corregimiento de Juanchaco, Valle del Cauca, Colombia para el mes de Septiembre de 2017.
11 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 30-63 µm fraction.
185 records from Dinoflagellate cysts from sediment core PS2741-1.
79 records from Birdrace-Bielefinken-Bielefeld.
107 records from Müritz-Nationalpark.
125 records from Range table from ostracoda in ODP Hole 143-866B.
65 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-2.
1 records from Planktic foraminifera abundance of Hole 28-274.
913 records from Phytoplankton abundance in surface water in October 1997, Pisco, Peru.
146 records from Birdrace-Wannacks_Topti(c)ker-Lübeck.
270 records from Wald am Schloss Wittgenstein Bad Laasphe.
111 records from Megafauna abundance and biomass from trawl samples obtained during cruise DI237.
28 records from Stadtpark Prinzengarten (Sigmaringen).
210 records from Phytoplankton abundance at the sea bottom off Sechura in january 2007, Peru.
35 records from Phytoplankton abundance in surface water in 2003, Ancon, Peru.
68 records from Plasm bearing foraminifera counts of multinet M21/5_MSN729.
169 records from (Appendix A) Planktonic foraminifera abundances in ODP Site 138-852B.
41 records from Phytoplankton abundance at station Sechin_2003-10-03_2, Casma, Peru.
105 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2008.
743 records from Données naturalistes de François BRETON.
23 records from Schulgarten der Hainbuchenschule (Hagenbach).
222 records from (Table 1.2.2.1) Integrated abundance of sympagic meiofauna in sea-ice cores of Polarstern cruise ANT-XXIII/7.
20 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2004.
40 records from Plasm bearing foraminifera counts of multinet M21/5_MSN733.
210 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/108-3.
59 records from Schulhofuntersuchung Thomas-Mann-OS.
266 records from Ostracode ratios of adult single valves to adult specimens in surface sediment samples from the Persian Gulf (Table 1b).
14 records from Analyses of the recent components in the sand fraction of sediment core PS1013-1.
718 records from Range table from benthic foraminifers in ODP Hole 146-888B.
5264 records from (Table T1) Plankontic foraminifera stratigraphy of ODP Site 184-1143.
164362 records from DFO Maritimes Research Vessel Trawl Surveys Fish Observations.
2396 records from Leicestershire and Rutland Reptile Records to 2011.
33 records from Smear slide analysis on sediment core GeoB4214-1.
43 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-14.
98 records from Foraminifera species abundances from tow TT007_8-MOC15.
190 records from Planktic foraminifera abundance of Hole 74-525A.
130 records from BIRDRACE - The famous Grouse feat. The James.
374 records from Planktic foraminifera abundance of Hole 68-503B.
2398 records from University of Amsterdam (NL) - Páramo vegetation research, Central Andean Cordillera - Colombia.
63 records from Distribution of meiofauna in surface sediments of the Iberian deep sea basin (Table 3).
49 records from NSG Hellbachtal.
2155 records from Benthic foraminifera of sediment core MD99-2286.
26 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction 30-63 µm.
13650 records from Distribution of planktic foraminifera in surface sediments of the Atlantic Ocean (ATL947).
552 records from Phytoplankton abundance in surface water in August 1997, Pisco, Peru.
1 records from Recursos hidrobiológicos de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO.
6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-4.
144 records from Diet, Tidal and Vertical Variations of Phytoplankton and Its Environment in Frobisher Bay, Canada, 1980 and 1981.
143462 records from Waarnemingen.be - Non-native plant occurrences in Flanders and the Brussels Capital Region, Belgium.
265 records from Coarse fraction analysis and texture of biogenous sands from Josephine Seamount surface samples (Table 2).
15 records from Ostracoda abundance of Hole 48-404.
592 records from (Table 2) Raw counts of planktonic foraminiferal species and varieties from the sediment surface samples from the South China Sea.
14 records from Microzooplankton abundance and biomass at station NBP97-08-03-3.
18 records from Schulgarten der Gesamtschule Am Heidberg.
22 records from Coccolith counts of multinet SO119_MSN1272.
1215 records from (Table 1) Distribution of planktonic foraminifera from samples spanning the Cretaceous-Tertiary boundary at ODP Hole 207-1259C.
153 records from Benthic meiofauna abundance in surface sediment of core PLG93_BCORE1.
480 records from (Tab. 6) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 41-370, Deep Basin West off Morocco.
68 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart).
5 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf.
584 records from Registro de murciélagos del Cañón del Chicamocha, Santander (2013 - 2014).
965 records from Nannofossil abundance of Hole 75-532.
62 records from Données de Mammifères marins en Polynésie française issues du South Pacific Whale Research Consortium.
15 records from Microzooplankton abundance and biomass at station NBP97-08-29-1.
33 records from Plasm bearing foraminifera counts of multinet POS231/3_MSN1329.
25 records from Planktic foraminifera counts of sediment core ELT48.022-PC.
36 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 30-63 µm fraction.
79758 records from natagora-earlybirds.
32 records from Abyssal fauna of the UK-1 polymetallic nodule exploration claim, Clarion-Clipperton Zone, central Pacific Ocean: Echinodermata.
1246895 records from Observations floristiques floutées issues de la base de données flore du Conservatoire botanique national alpin.
144 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 189-1172A.
18 records from Range table from planktonic foraminifers in ODP Hole 167-1010B.
140 records from Planktic foraminifera counts at CTD station PS55/019.
62 records from Total foraminifera counts of multinet M21/4_MSN705.
397 records from Données naturalistes du Comité départemental de l'Essonne (CODEP91) de la Fédération Française d'Etudes et de Sports Sous-Marins.
253 records from Nannofossil abundance of Hole 39-355.
1286 records from Conservación de la guacamaya verde (Ara militaris) en la Reserva de la Biósfera Tehuacán-Cuicatlán, México: un estudio de abundancia y reproducción en la zona de la cañada.
113 records from Electron Micrograph Database - Terrestrial and Limnetic Specimens.
238 records from Naturerlebnisraum Koppelsberg.
364 records from Nannofossil abundance of Hole 85-573.
8 records from Abundance and carbon biomass of phytoplankton at station TT007_9-CTD113.
141 records from Biodiversity survey of Rugezi wetland, Year 2013.
449 records from Artsprosjekt Pyrenomycetes.
1026 records from EEIKO Base de datos sobre plantas invasoras.
1577 records from (Table 2) Stratigraphic distribution of dinocyst taxa in ODP Hole 150-903A.
168 records from Assemblage of living benthic foraminifera in sediment core GeoB4916-4.
33 records from Microzooplankton abundance and biomass at station TT043_27-1.
11086 records from (Table 2) Distribution of late Miocene to Pleistocene calcareous nannofossils in ODP Hole 105-646B.
17 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-5.
74 records from Nannofossil abundance of Hole 94-610C.
570 records from Relative abundances of middle Pleistocene benthic foraminifera in DSDP Site Site 90-594.
173 records from Renaturierung Werse (Innenbereich Beckum).
23 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1a.
1561 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Dana00/5.
120 records from Total foraminifera counts of multinet SO118_MSN1267.
466 records from Nannofossil abundance of Hole 4-31.
48 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1197.
14 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_3-CTD4.
6285 records from Time slice 2 of planktic foraminifera of the last glacial maximum.
24 records from RNF - Données de la Réserve Naturelle du Marais de Lavours.
1040 records from Foraminifera and ostracods profile from sediment core AV14_K2-3.
140 records from (Table 2) Occurrence of upper Maestrichtian to Eocene benthic foraminifers in ODP Hole 121-753A.
47 records from Records of Giant Silkmoths (Saturniinae) from Vermont Collections and 2002-2007.
927 records from Distribution of major planktic foraminifer at Site 177-1092.
49 records from Foraminifera species abundances from tow TT011_15-MOC78.
1627 records from TransForest vegetation data.
201 records from Biodiversity of springs and rock seepages 2003.
127 records from Microzooplankton abundance measured on water bottle samples at station PS65/466-2.
4 records from Planktic foraminifera abundance of Hole 23-225.
35 records from Benthic foraminifera abundance of Hole 56-434.
63 records from Planktic foraminifera counts of sediment core V19-204.
28 records from Black grouse lek survey in Moray and Nairn 2009.
2 records from Catalogue Lhomme 1923-[1963].
521 records from Schanzenanlage Bergham.
140 records from Planktic foraminifera abundance of Hole 37-332.
48 records from Dörnberg.
2205 records from (Table 2) Calcareous nannofossil distribution in the Upper Cretaceous of ODP Hole 120-748C.
4 records from Distribution of Quinqueloculina sp. in sediment core 13200-025.
200 records from (Table 7) Ranges of benthic foraminifers through the Oligocene in DSDP Hole 26-253.
98 records from Total foraminifera counts of multinet POS231/3_MSN1332.
38 records from Bean geese on the Slamannan Plateau, Central Scotland between 1993 and 1995.
75 records from The interstitial subsoil fauna of the lower beach level at Sarso Beach, Red Sea (Table 4).
234 records from Données Phesulma borbonica du Parc national de La Réunion - COBE03.
909 records from Phytoplankton abundance and species composition in the Tyrrhenian Sea in November 1981.
123 records from Abundance of dead benthic foraminifera in sediment core CD86_06_BC5.
1268 records from Antarctic Krill occurrence data from US AMLR "US Antarctic Marine Living Resources" Program.
313 records from Phytoplankton abundance at bottle station A3/66A.
200 records from Range table from benthic foraminifers in ODP Hole 149-900A.
132 records from Plasm bearing foraminifera counts of multinet M21/1_MSN613.
6 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B2_820-4.
32 records from Freshwater Gwyniad Survey Data.
27 records from Nannofossil abundance of Hole 10-85.
1052 records from Nannofossil abundance of Hole 37-334.
57 records from Schulgelände SGD/Viersen.
7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald.
322 records from Nannofossil abundance of Hole 84-570.
670 records from Bulau.
936 records from (Table 1) Distribution of calcareous nannofossils at ODP Hole 125-781A.
88 records from Great Crested Newt Special Area of Conservation (SAC) Monitoring Data.
53 records from Leopard and Weddell seal program 1999/2002.
4309 records from Données naturalistes de Ségolène FAUSTEN.
54 records from Distribución, abundancia y efectos nocivos de tres especies de plantas invasoras.
196 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB04 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates.
678 records from Percentages of planktonic foraminifera species in sediment core RC24-27.
9517 records from 2010-2013 Beetle Data from Machair LIFE+ Project Plots.
64173646 records from Artportalen (Swedish Species Observation System).
172 records from Foraminifera abundance of sediment core MD81-LC07.
461 records from Range table from planktonic foraminifers in ODP Hole 182-1134A.
403 records from Range table from benthic foraminifers in ODP Hole 181-1119C.
163 records from Nannofossil abundance of Hole 28-265.
72 records from Lebensraum Fluß/Zwickauer Mulde in Wolkenburg.
1 records from Karpfenteich, Klasse 6d.
6 records from Range table from planktonic foraminifers in ODP Hole 145-883C.
179 records from Total foraminifera counts of multinet SO117_MSN1244.
116 records from Total foraminifera counts of multinet M10/2_MSN334.
24 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/324-1.
6891 records from SEWBReC Grasshoppers, Bush-crickets and allies (South East Wales).
64 records from Range table from planktonic foraminifers in ODP Hole 172-1063A.
44 records from Planktic foraminifera abundance of Hole 40-361.
5743 records from Queensland Museum provider for OZCAM.
417 records from Loup 2016 présence occasionnelle communale (réseau Loup-Lynx ONCFS).
71 records from Range table from planktonic foraminifers in ODP Hole 182-1133C.
69 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1379.
119 records from (Table 5) Planktonic foraminifera genera assemblage at DSDP Hole 80-548A.
192 records from (Table 3) Absolute concentrations and raw counts of seven genera of dinoflagellate in ODP Site 170-1039.
708 records from EDP Baixo Sabor: Herpetology – Baseline Studies [2009].
1 records from Molche in Ruschwedel.
96 records from Plasm bearing foraminifera counts of multinet M21/1_MSN620.
31 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 1998.
488 records from Planktic foraminifera counts of sediment core V23-100.
107 records from Range table from benthic foraminifers in ODP Hole 146-889B.
43293 records from Données naturalistes d'Olivier ESCUDER.
701 records from Données naturalistes d'Arnaud LE NEVÉ.
2141 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia.
221 records from Abundance of planktic foraminifera at CTD station M39/4_404CTD-57.
3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-MNB6.
39 records from Nannofossil abundance of Hole 16-155.
20416 records from Zomerganzen - Summering geese management and population counts in Flanders, Belgium.
12 records from Analyses of the recent components of sediment core PS1219-1.
111 records from Nematode densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC02.
456 records from Late Pleistocene planktonic foraminifera of Hole 302-M0004C (Addendum 1).
717 records from Redland City Council Citizen Science Portal.
180 records from Caracterización de algas y comunidad íctica de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO.
311 records from HBRG Invasive Non-native Plants Dataset.
222 records from Planktic foraminifera counts of sediment core RC11-126.
163 records from Steinbruch Mainz-Weisenau, 3. Jahr.
166 records from Zielbach (Töll).
96 records from BIRDRACE Emslandracer.
806 records from Pollen profile V and Ausfluss at Krumbach, Germany.
2242 records from SEWBReC Worms (South East Wales).
229 records from Queen Charlotte Sound / Tōtaranui and Tory Channel / Kura Te Au (HS51) Hydrographic Survey Marine Mammal Observations.
355 records from Abundance of Polychaeta species in surface sediments of the east Greenland continental slope (75° N section).
116 records from Foraminifera species abundances from tow TT007_12-MOC21.
58 records from Schulgelände Kranich-Gymnasium (Salzgitter).
23 records from Record of 7 acritarch taxa from the Miocene, Pliocene and Pleistocene of ODP Hole 151-910C.
125 records from (Table 2) Absolute abundance of Contusotruncana contusa in DSDP Hole 74-525A.
2352 records from (Table 10) Distribution of Pleistocene to late Miocene nannofossils in ODP Hole 108-664A.
9264 records from Big Island Invasive Species Committee - Pest Reports - 2005-2010.
3010 records from Données CardObs (hors programme spécifique).
62 records from Range table from planktonic foraminifers in ODP Hole 183-1139A.
10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station MARCH-1995-D4.
36 records from Ice Algae Barents Sea.
441 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-959D.
353 records from (Table 1) Fossil record of foraminifera and ostracoda from Albersdorf clay pit, north Germany.
937140 records from PlutoF platform observations.
1520 records from (Table 2) Stratigraphic occurrence of selected diatom species from DSDP Hole 12-112.
239 records from Nannofossil abundance of Hole 94-611D.
136 records from Total foraminifera counts of multinet M21/6_MSN784.
8 records from Benthic macrofauna abundance of sediment core 13078-015.
84 records from (Appendix B) Calcareous benthic foraminifers in ODP Hole 123-765C.
99 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Annelida, Arthropoda, Bryozoa, Chordata, Ctenophora, Mollusca.
477 records from Pollen profile from sediment core AV14_K2-1.
1 records from Revisión de las Agavaceae (sensu stricto), Crassulaceae y Liliaceae incluidas en el PROY-NOM-059-ECOL-2000.
24 records from Coccolith counts of multinet M32/5_MSN977.
238 records from Données Mammifères marins Aquasearch - Dauphin Passion.
1249 records from (Table 2) Biostratigraphy of marine benthic and planktonic taxa in sediment core GIK14350 near Dagebüll, northern Germany.
83 records from Nannofossil abundance of Hole 10-89.
278 records from Nannofossil abundance of Hole 30-285A.
82 records from DREAL_PACA_-_N2000_-_Ville_de_Fréjus_2017_12_18.
23035 records from WTSWW Data: All Taxa (West Wales).
7 records from Fichas diagnósticas para 10 especies de anfibios y reptiles mexicanos.
412318 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía.
192 records from "Ahrschleife bei Altenahr".
96 records from (Table 2) Sea surface temperature reconstruction from sediment core MD88-770.
4989 records from South Australian Museum Australia provider for OZCAM.
35 records from Urwald 3 (Bad Waldsee).
35 records from Plasm bearing foraminifera counts from multinet M32/3_MSN957.
55539 records from Seasearch Marine Surveys in Ireland.
5 records from Coccolith counts of multinet M32/5_MSN981.
220 records from (Table 1) Distribution of planktonic foraminifers in ODP Hole 126-787B.
1788 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise DeHolland1986.
103702 records from Marine Commercial Fish Survey (FV Kapala, FV Trader Horn, FV Shelley, FV Kirrawa, FV May Bell) in the East and South East Australian Region from 1975 to 2008.
69 records from Unter hellen Zinnen und finsteren Grotten.
16 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea).
309 records from Planktic foraminifera abundance of Hole 23-225.
1003 records from (Table 2) Distribution of planktic foraminifera in early Paleogene sediments of DSDP Hole 27-259, Perth Abyssal Plain off Western Australia.
34981 records from HBRG Vertebrates (not Badger) Dataset.
134 records from Range table from planktonic foraminifers in ODP Hole 177-1089B.
6173 records from SPC PROCFish/C Fish Observations New Caledonia 2004.
6446 records from Modernisation des ZNIEFF du PnrL.
16 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD20.
2 records from Microzooplankton abundance and biomass at station TT050_25-4.
3422 records from Highland Breeding Bird Data 2002-2003 - non-sensitive breeding species.
616 records from (Table 15) Distribution of planktonic foraminifera in the early to early late Oligocene section of ODP Hole 149-900A.
63 records from Tasmanian Museum and Art Gallery provider for OZCAM.
276 records from Mokihinui River Hydro Proposal.
61 records from Inventario Murciélagos Finca Naranjito, Aracal, Yopal, Casanare.
5 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, >125 µm fraction.
102 records from (Table 4b) Range chart of benthic and planktonic foraminifera of ODP Hole 127-796B.
740 records from Monitoring data of marine turtles on the Togolese coast over 2012-2013 years.
2 records from Benthic foraminifera abundance of Hole 42-376.
55 records from Seeufer ehem. BUGA-Gelände.
754 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC12-294.
1024 records from HBRG P.F. Entwistle Notebooks Dataset.
55 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Cragbank and Wolfehopelee SSSI.
534 records from Leopard Seal census, Heard Island 1987/88.
6 records from Range table from benthic foraminifers in ODP Hole 178-1100D.
1189 records from kerkyra.
552 records from Percentages of planktonic foraminifera species in sediment core RC24-7.
102 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360.
1450 records from Données naturalistes d'Alain BERLY.
6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5.
813 records from Ville de Trois-Rivières - Bioblitz 2012.
637 records from Inventaire de l'îlot du Lédénez Vraz.
37 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey.
368 records from Ring ouzel national sample survey in the UK in 1999.
2240 records from (Figure 7) Distribution chart of benthic foraminifers in ODP Site 126-793.
1698 records from Red-throated diver national surveys in Scotland - raw data.
215 records from (Table S2) Nannofossil abundances at DSDP Hole 86-577A.
64 records from Assemblage of living benthic foraminifera in sediment profile GeoB4913-4.
35 records from Phytoplankton abundance at station Sechin_2003-11-06_2, Casma, Peru.
14821 records from Données bibliographiques et opportunistes Mammifères issues du SiRF.
131 records from BIRDRACE Brut.
565667 records from Données de la flore d’Alsace (SBA).
160 records from Succession of benthic hard-bottom communities abundance at station Errina2012_AG.
72 records from Birdrace-Buteo2DO-Dortmund.
1338 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV).
45 records from Total foraminifera counts of multinet M21/4_MSN719.
1704 records from DREAL Auvergne - Insectes - 2015.
380 records from (Table 3d) Foraminiferal distribution chart of petroleum well Great-Eastern-1.
24 records from Planktic foraminifera assemblage in sediment core GIK23066-2.
26185 records from Données de Mammifères enregistrées dans BazNat - Lot 1.
51 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/009-2.
51 records from University of Amsterdam (NL) - Páramo Vegetation Research, Bordoncillo - Nariño, Colombia.
1647 records from Nannofossil abundance of Hole 17-167.
12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_3-CTD39.
82 records from Range table from planktonic foraminifers in ODP Hole 169-1038I.
2744 records from Distribution of major planktic foraminifer at Site 177-1090.
122 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB02 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms.
359 records from Pöhlberg bei Annaberg.
1924 records from Caracterización de la vegetación en una zona delimitada en Cumbitara, La Llanada, Policarpa y Los Andes Sotomayor (Nariño), como insumo para la identificación de oportunidades de conservación para la recuperación de los servicios ecosistémicos de bosque seco.
7 records from Plasm bearing foraminifera counts of multinet POS231/3_MSN1336.
64 records from "Wildnis erleben" - "Vielfalt erlebbar machen" - Botanischer Garten u.Chrimmitschauer Wald.
132 records from (Table 9) Dinoflagellate cyst species distribution in ODP Hole 112-684B.
104 records from Birdrace-RMD_Die_Gipfelstürmer-Main-Taunus-Kreis.
5 records from Gewässeruntersuchung (Prien) mit Kl. 4b.
102164 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007.
4 records from Microzooplankton abundance and biomass at station TT050_11-4.
11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI.
12 records from Range table from planktonic foraminifers in ODP Hole 151-912A.
231 records from Total foraminifera counts from multinet M32/5_MSN976.
4698 records from (Table 10) Eocene-Oligocene diatom biostratigraphy of ODP Hole 120-748B.
4227 records from Données naturalistes de Loïc SALAUN.
373 records from Dinocyst occurrences and zonations from IODP Hole 313-M0029A.
452 records from Planktic foraminifera abundance of Hole 22-214.
1255 records from (Table 6) Planktonic foraminifera in ODP Holes 139-856A and 139-857A.
4 records from Distribution of Quinqueloculina sp. in sediment core 13077-023.
2507 records from East Ayrshire Species Database.
2565 records from (Table 1) Distribution of early late Eocene fossil content in ODP Hole 115-715A.
1200 records from Phytoplankton abundance in surface water in June 1997, Callao, Peru.
12 records from Nano and microzooplankton abundance and biomass at station NBP97-01-14-2.
9 records from Sarcodine counts and carbon biomass at station TT011_6-CTD71.
1030 records from Benthic foraminifera and algae abundance of Hole 81-555.
195 records from Benthic macrofauna abundance of subcores of sediment core 13078-015.
2843 records from (Appendix C) Stratigraphic range and relative abundance of Neogene planktonic foraminifer taxa in ODP Hole 120-751A.
2196 records from Ecology, structure and dynamics of private plantations of Teck (Tectona grandis Lf) of the Department of the Atlantic (South Benin), 2011.
1136 records from (Table 1) Distribution of agglutinated benthic foraminifera in lower Cretaceous sediments of DSDP Hole 27-263 in the Cuvier Abysaal Plaine, Indian Ocean.
16 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México.
13 records from Analyses of the recent components of sediment core PS1422-1.
320 records from (Table S1) Nannofossil abundances at DSDP Hole 86-577.
12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_1-CTD8.
607 records from Inventory of Bassila forest (North-Benin).
406 records from Pollen profile from Muscotah Marsh B.
48 records from Catch related distribution of Appendicularia at station M9_C near the Great Meteor Bank, Northeast Atlantic (Table 8).
3 records from Dinoflagellate abundance of Hole 85-572A.
718 records from Planktic foraminifera assemblage of sediment core ELT49.023-PC.
120 records from (Table 10) Occurrence of benthic foraminifera in ODP Hole 112-688E, Part II.
15 records from Range table from planktonic foraminifers in ODP Hole 182-1129A.
323 records from (Table 1) Distribution and numerical abundance of foraminifera of sediment core CRP-3.
1408 records from (Table 2) Distribution of Campanian-Maestrichtian agglutinated foraminifers in DSDP Hole 78-543A.
135 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/038-3.
496350 records from CRBPO : STOC, Baguage.
6 records from Foraminifera abundance of Hole 58-442.
229 records from Vorderer Tiergarten (Dessau).
253 records from Données naturalistes d'Olivier LAURENT.
22728 records from Restauración y conservación de Isla Guadalupe.
12 records from Kindergarten.
258 records from Systematic census of the private plantations of the firewood of the Benin ..
29036 records from Mosses and Liverworts: Records for Kent..
585 records from (Table T2) Calcareous nannofossil stratigraphy in ODP Hole 186-1151C sediments.
59335 records from USGS South Florida Fish and Invertebrate Assessment Network Crustaceans.
96 records from Warnowtal (Rostock).
972 records from (Table 2) Distribution of benthic foraminifera on sediment core PS2138-1.
6 records from Wuhle - Brücke / B1.
8 records from Benthic macrofauna abundance of sediment core 12930-068.
48 records from SNH Invertebrate Site Condition Monitoring 2015: Tweedwood - Gateheugh SSSI.
475 records from Relative abundance of dead benthic foraminifera in the large size fraction of surface sediment off NW Africa (Table 4).
112 records from iHerbarium.
23 records from Planktonic foraminifera in ODP Hole 112-688A (Table 1).
10082 records from Données "faune" de la Société Nationale de Protection de la Nature (SNPN) pour le SINP île de France.
40 records from Abundance of benthos infauna at station GIK23013-2.
111 records from BIRDRACE Die Wendehälse.
55 records from Mauervegetation,Flechten und anderes.
213 records from Abundance and biomass of phytoplankton in Butakova Bay, Aral Sea, in september 1990.
281 records from Feriendorf des Kreises Groß-Gerau Ober-Seemen/Gedern.
1021 records from Phytoplankton abundance and species composition in the Gulf of Naples and the Gulf Salerno in November 1985.
24 records from Range table from benthic foraminifers in ODP Hole 139-858D.
101 records from In situ observations of Stygiomedusa gigantea.
8332 records from Scotland Otter Survey Database.
19 records from Antarctic Krill occurrence data from Japanese expeditions.
8914 records from Balsfjord Nature Reserves.
39 records from Macrofauna biomass in surface sediment sampled during cruise DI231.
656 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas.
922 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC11-86.
8 records from Analyses of the recent components of sediment core PS1401-2.
186 records from Benthic foraminifera and algae abundance of Hole 81-554.
42 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf.
57 records from verschiedene Kleingewässer um Oldenburg/Holstein.
24 records from Range table from benthic foraminifers in ODP Hole 178-1103A.
216664 records from Carnet B Lorraine.
1768 records from (Table 7) Distribution of dead benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 1.
480 records from Relative abundance of live (Rose Bengal stained) benthic foraminifera in East Atlantic surface sediments off Senegal and Gambia (Table 1).
451 records from Counting of benthic foraminifera of ODP Hole 182-1132B.
5 records from Nannofossil abundance of Hole 16-157A.
553 records from Radiolaria assemblage in sediment core GIK23414-6.
116 records from (Table 3) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Hole 92-598.
321645 records from Seasearch Marine Surveys in England.
38 records from Planktic foraminifera abundance of Hole 84-566C.
1221 records from Siliceous microfossil occurrence, Site 177-1088.
61 records from BIRDRACE Kollektiv Eisente.
26695 records from Fishes in MZNA-VERT: cyprinid and salmonid communities in the rivers Erro and Urederra (Spain). PhD project, Cristina García-Fresca.
439 records from Diatom abundance measured on water bottle samples at station PS58/107-5.
1507 records from Mammal records captured from Licence Returns submitted to Natural Resources Wales.
160 records from Nannofossil abundance of Hole 15-150.
160 records from Integrierte Gesamtschule Flensburg Wiemoosgraben.
920 records from SEWBReC Slime Molds (South East Wales).
115 records from Nannofossil abundance of Hole 1-3.
130 records from Abundances of dinoflagellate cysts in sediment trap MST-9 (Appendix 1).
78 records from Phytoplankton abundance at station Rigel_1_2005-07 in July 2005, Chipana, Chile.
147 records from Nannofossil abundance of Hole 6-55.
1177 records from Inventaire des Lépidoptères Rhopalocères et Zygènes de France métropolitaine.
122 records from Total foraminifera counts from M35/1_MSN1060.
4175 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690.
798 records from Planktic foraminifera abundance of Hole 27-262.
4288 records from (Figure 5) Range chart of selected dinocysts and acritarchs of ODP Hole 104-642A.
39 records from Planktic foraminifera abundance of Hole 27-260.
2536 records from Invasive Alien Species Occurrence in Ghana.
63364 records from CCAMLR historic KRILL.
94 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2139-1.
124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis.
5817 records from Diversité des Poissons de Nouvelle-Calédonie, pêche à la roténone.
10695 records from Records of the Australian National Botanic Gardens Seedbank.
13 records from Espèces envahissantes de la Guinée forestière extraites dans la base de données de CRRA Sérédou Macenta, IRAG..
106 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango).
87901 records from MDFRC macroinvertebrate survey.
313 records from RHS Fuchsia Gall Mite (Aculops fuchsiae) monitoring.
827 records from Schatzinsel Norderney.
93 records from Plasm bearing foraminifera counts from multinet SO119_MSN1284.
43 records from Nannofossil abundance of Hole 25-249.
63 records from Phytoplankton abundance at station Rigel_3_2005-04 in April 2005, Chipana, Chile.
372 records from Abundance of living coccolithophores in the northern Arabian Sea (Table 2).
4536 records from (Table 3B) Occurrence and estimated abundance of planktonic foraminifers at DSDP Holes 85-572C and 85-572D.
8615 records from CSIRO, Tropical Zooplankton Biomass and Composition, Albatross Bay - Gulf of Carpentaria, North Australia 1986-1988.
100 records from Microzooplankton abundance measured on water bottle samples at station PS65/514-2.
228 records from Assemblage of dinoflagellate cysts analysed in surface sediment samples off Peru.
824 records from Données naturalistes de Philippe RAVAT.
19 records from Occurrence of recent nannoplankton in surface sediments at M1_MULT243, Arabian Sea (Fig. 2).
109 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1193.
24 records from SNH Invertebrate Site Condition Monitoring 2013/14: Dollar Glen SSSI.
32660 records from The national database for marine data (MADS).
57 records from Nannofossil abundance of Hole 9-82.
204 records from Foraminifera abundance of Hole 57-440A.
13 records from Microplankton counts and carbon biomass at station TT008_5-CTD18.
19 records from Description of lithologic section units of IODP Hole 325-M0035A.
59 records from (Table IIIa) Planktic foraminifera abundances in the latest Cretaceous sample interval of DSDP Hole 86-577 from the Shatsky Rise, western Pacific Ocean.
2332 records from (Table 4) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-503A from the East Pacific Ocean.
900 records from North Atlantic (Rockall Plateau) coccolith assemblage data for MIS 5 of ODP Hole 162-980B.
62 records from Kabelskebach (Kabelsketal, Saalkreis).
104 records from Pollen analysis of sediment core GeoB1007-4.
668 records from Freshwater Macrophyte Survey Data.
102 records from (Table 5) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-600.
90 records from Plasm bearing foraminifera counts of multinet M21/2_MSN639.
288 records from Size of planktic foraminifera at CTD station M39/4_402CTD-55.
55 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, 63-125 µm fraction.
447 records from Gelände des IVL (Zeckern).
48 records from Fauna herpetológica de los Parques Ecológicos Distritales Humedales Bogotá, D.C..
1202 records from Planktic foraminifera abundance of Hole 72-516A.
114 records from (Tab. 5) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 41-367, Cape Verde Basin.
86 records from Range table from benthic foraminifers in ODP Hole 172-1060A.
13 records from Warnowufer Groß Klein.
153 records from Planktic foraminifera abundance of Hole 18-181.
220 records from (Table 4) Distribution of calcareous nannofossils at ODP Hole 125-785A.
14 records from Foraminifera abundance of Hole 60-453.
12 records from Planktic foraminifera abundance of Hole 42-372.
4674 records from (Table 2) Distribution of Cretaceous nannofossils at DSDP Hole 79-545.
44051 records from Alterra (NL) - Entomofauna inventory in peat swamps.
237 records from Evaluación del ámbito hogareño y calidad de hábitat del borrego cimarrón (Ovis canadensis mexicana), Berrendo sonorense (Antilocarpa americana sonoriensis) y del Puma (Felis concolor) en la Reserva de la Biósfera El Pinacate y Gran Desierto de Altar.
1004 records from Dead benthic foraminifera of surface sediments from the East Atlantic continental margin off Portugal (Table 5 & 7).
16 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-11-5.
318 records from Pollen data of trap CB4.
996 records from Phytoplankton abundance in surface water in July-August 1996, Pisco, Peru.
1481 records from Leicestershire and Rutland Mature trees Inventory 2011.
11 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0004C.
1847 records from Données diverses du PnrL.
48 records from SYMBIOSE_2017_12_18.
2363 records from Avifauna en un área perturbada del bosque andino en el Parque Nacional Natural Farallones de Cali, corregimiento de Pance, Valle del Cauca (Colombia).
747 records from Caracterización del hábitat y patrones de distribución del gorrión serrano (Xenospiza baileyi) en el sur del Valle de México.
6160 records from (Table 10A) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-588.
56 records from Phytoplankton abundance at station Rigel_5_2005-02 in Febraury 2005, Chipana, Chile.
290 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-14.
136 records from Abundance of planktic foraminifera at CTD station PS55/080-1.
384 records from "Schwarzwassertal" bei Pobershau.
1932 records from (Table 5) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583D.
5 records from Microfossil abundance of Hole 21-208.
7 records from Analyses of the recent components in the sand fraction of sediment core PS1278-1.
3737 records from SEWBReC Algae and allied species (South East Wales).
3336 records from (Table 14) Calcareous nannofossil occurrences in ODP Hole 130-806B.
57647 records from Belgian Coccinellidae - Ladybird beetles in Belgium.
1773 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612.
1211 records from CSIRO, Cruise SS199101, Marine Biology Data, Western Australia, 1991.
3 records from Distribution of Quinqueloculina sp. in sediment core 13200-078.
1 records from Microplankton counts and carbon biomass at station TT011_4-CTD46.
633 records from Records of otters from Site Condition Monitoring in Scotland 2011-2012.
127 records from Faunal assemblage of sediment core TR149-35.
6133644 records from iNaturalist Research-grade Observations.
143 records from (Table 2) Dinocyst specimens per slide and relatice abundances in each sample of ODP Hole 120-748C.
8928 records from City of Amsterdam (NL) - Fyke Fishing Piet Ruiter.
65 records from Cuxhaven Schlosspark, Klasse 5e- Amandus-Abendroth-Gymnasium.
11571 records from (Table 5) Stratigraphic distribution of calcareous nannofossil taxa in ODP Hole 149-898A.
193 records from Nannofossil abundance of Hole 41-366A.
84 records from (Table 2) Absolute abundance of Contusotruncana contusa in DSDP Hole 72-516F.
6 records from Nannofossil abundance of Hole 31-298A.
46664 records from Fife non-breeding bird 5km atlas 1991-99.
85338 records from Diversidade e ocorrência de peixes em Inhambane (2009-2017).
2340 records from (Figure 10) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644B.
1716 records from (Figure 9) Distribution of Cretaceous planktonic foraminifers and associated organisms from DSDP Hole 77-536.
244 records from (Table 1) Abundance of planktonic foraminifera in ODP Hole 113-689B, large size fraction.
2623 records from SPC CoFish Fish Observations Niue 2005.
507 records from Planktic foraminifera abundance of Hole 84-567A.
208 records from Nannofossil abundance of Hole 39-359.
1857 records from Range table from planktonic foraminifers in ODP Hole 159-960C.
31 records from Phytoplankton abundance in surface water in 2004, Ancon, Peru.
4159 records from DBG Mirabilis rotundifolia Demographic Monitoring.
1 records from Synthèse de la Répartition des populations de cerf élaphe en 1995 (réseau Ongulés sauvages ONCFS-FNC-FDC).
3 records from Range table from planktonic foraminifers in ODP Hole 178-1102C.
367 records from ARKO.
1500 records from Esponjas, corales escleractinios, equinodermos y peces de arrecifes coralinos del norte y sur de Veracruz.
70786 records from Atlas of Life in the Coastal Wilderness - Sightings.
128 records from (Appendix F) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-749C.
172 records from Nannofossil abundance of Hole 49-412.
26 records from Abundance of benthos infauna at station PS1240-1.
611 records from Données du Râle gris sur le territoire de la Guadeloupe.
8368 records from Records of the Queensland Plant Pathology Herbarium.
29 records from Amphipoda Hyperiidea of the Southern Ocean: catalogue and occurrences.
12 records from Microzooplankton abundance and biomass at station NBP97-03-12-2.
18 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5120-2.
94 records from Birdrace-Erlanger_Piepmätzchen-Erlangen/Höchstadt.
110 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB07 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates.
1135 records from MarineGEO visual diver surveys of fish communities around Carrie Bow Cay, Belize, 2015.
694 records from Polish seed gene bank – historical passport data of accessions.
64 records from Westerwälder Umwelt- und Naturschutztag an der Fuchskaute im Westerwald.
168 records from (Table 2) Distribution of selected planktonic foraminifer species at ODP Site 124-770.
1290 records from (Table 8D) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 89-586B, Sections 15-4 through 19-3.
32 records from Nannofossil abundance of Hole 3-22.
1800 records from (Table 8) Pliocene nannofossil range chart for ODP Hole 134-833B.
3063 records from Données entomologiques sur la Réserve Naturelle de l’Étang Noir. (Seignosse, Landes). Bilan des études 2001 à 2009.
2 records from Hildener Heide - Spörkelnbruch (Haan).
105 records from Peces y Mamíferos de la región de Norogachi, Alta Sierra Tarahumara, Chihuahua.
5406 records from Données Lépidoptères de l'Auvergne transmises par Pascal Peyrache..
8190 records from (Table 7) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-709C.
351 records from Küstenschutzwald.
134 records from BIRDRACE Griffin Wood Warblers.
9 records from Planktic foraminifera abundance of Hole 94-611B.
1736 records from Relative abundance of planktic foraminifera in sediment core GeoB1312-2.
45 records from Range table from benthic foraminifers in ODP Hole 146-891A.
65 records from Abundance of living benthic foraminifera in sediment core CD86_05_BC5.
1888 records from Benthic foraminifera and nannofossil abundance of Hole 40-360.
227 records from Data on cetacean strandings (1999 - 2014) on the Ukrainian coast of the Black Sea and the Sea of Azov and adjoining areas.
128 records from Faunal assemblage of sediment core TR149-32.
29 records from Brenz (Heidenheim).
1498 records from Nannofossil abundance of Hole 15-149.
232 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal.
134 records from Total foraminifera counts of multinet M21/6_MSN785.
1596 records from Registros Primates Neotropicales Convocatoria APC.
111 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V27-86.
19 records from Benthic macrofauna abundance of sediment core 13200-004.
16562 records from Records of Invasive Non Native Species held on the Cofnod database.
52 records from BIRDRACE Taubenhaucher.
4508 records from Contribution à la gestion durable des forêts : Caractéristiques écologiques et structurales de la forêt naturelle d’Akpè (Lama) au Sud du Bénin..
134 records from Planktic foraminifera counts at CTD station PS55/079-1.
130 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/012-5.
36 records from Schulgelände Lise Meitner Realschule (Paderborn).
111 records from Birdrace-Uhulogen-Lippe.
31 records from Kurler Busch (Scharnhorst).
8 records from Analyses of the recent components in the sand fraction of sediment core PS1014-1.
380 records from (Appendix A) Planktonic foraminifera abundances in ODP Site 130-807B.
9 records from Sarcodine counts and carbon biomass at station TT011_5-CTD64.
383 records from Neogene palynomorpha from site 81-555.
369 records from BIRDRACE Havelland.
83 records from Birdrace-Die_Vogelscheuchen-Herford.
136 records from Birdrace-SpeedBirder-Zwickauer_Land.
18 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB02 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups.
311 records from Benthic foraminifera abundance of Hole 41-366A.
370 records from Otter survey of Ireland 2004 & 2005.
13 records from Planktic foraminifera abundance of Hole 17-165.
1055 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands.
74 records from Phytoplankton abundance measured in surface water during Charles Darwin cruise CD85.
12208 records from (Table T7) Calcareous nannofossil stratigraphy of ODP Hole 198-1210B.
111099 records from Suivi Temporel des Rhopalocères de France (STERF).
14 records from Microzooplankton abundance and biomass at station NBP97-08-09-1.
375 records from MalaCo, Journal de Malacologie continentale [2005-].
23 records from Australian Museum Ichthyology - 2012 Inscription Point.
144 records from Total foraminifera counts of multinet POS247/2_MSN1386.
411 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 113-690C, large size fraction.
23 records from Landwehrbach.
909 records from (Table S1) Relative abundances of coccolithophore taxa in surface sediment samples from the Equatorial and Southeastern Pacific.
9781 records from CSIRO, fish surveys by the Soela, 1980s.
602 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2.
42965 records from The census of national forest of Benin ..
72 records from Planktic foraminifera abundance of Hole 84-569A.
29 records from Birkenpilz.
124 records from Birds of Grand Kru Liberia.
1339 records from Microfossil abundance of Hole 16-158.
97 records from Nematode densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03.
27 records from Données naturalistes de Philippe VEILLON.
50 records from Weidegut Rechab.
583 records from Nannofossil abundance of Hole 78-543.
1136 records from CSIRO, Jack Mackerel surveys, 1978.
1100 records from Avifauna de bosques nublados en la cordillera Occidental, departamentos del Valle del Cauca, Risaralda y sur de Antioquia..
986 records from (Figure 3) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 103-641A.
16 records from Observations issues des suivis Argos des phoques gris en Atlantique et Manche Mer du Nord.
35 records from Total foraminifera counts of multinet FCA97C_MSN1339.
15 records from City of Edinburgh Natural Heritage Service - Bonaly Moorland Moth Survey.
145 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/043-4.
507 records from Nannofossil abundance of Hole 66-490.
1198 records from Phytoplankton abundance in surface water in October 1997, Chimbote, Peru.
196 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100500.
1 records from Synthèse de la Répartition des populations de bouquetin des alpes en 2005 (réseau Ongulés sauvages ONCFS-FNC-FDC).
19294 records from New Zealand Biodiversity Recording Network.
1462 records from Avifauna en dos parches de bosque seco del departamento del Valle Cauca (Colombia).
1 records from Données naturalistes de CARON Nicolas.
515 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797.
733 records from (Table 14) Distribution of planktonic foraminifers in ODP Hole 108-665A.
14 records from (Table 4b) Abundances of Globorotalia menardii in sediment core INMD-111BX.
10 records from Dinoflagellate abundance of Hole 81-552.
50 records from Abundance of epibenthic echinoderms at seafloor photography station POS196_1018.
1445 records from Pollen analysis of sediment profile SI0 from Siethener See.
42 records from Table 1. Location, water depth, grain size distribution, organic carbon and carbonate contents of the investigated Arctic and Antarctic surface sediment samples.
270 records from Range table from planktonic foraminifers in ODP Hole 180-1115C.
118 records from Total foraminifera counts of multinet POS231/3_MSN1329.
2350 records from Données naturalistes de Bernard Lalanne-Cassou.
134 records from Birdrace-Team_Havelland-Havelland.
1481 records from Nannofossil abundance of Hole 82-558A.
37 records from Planktic foraminifera counts of sediment core RC13-154.
3736 records from Sizing Ocean Giants.
3320 records from BioGIS - Mammals - SPNI.
29520 records from Inventaire et suivis d'espèces dans le Parc national des Cévennes.
90159 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados.
15 records from Diatom abundance of Hole 60-460.
23 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 30-63 µm.
18 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction.
914098 records from SEWBReC Birds (South East Wales).
861 records from (Table 1) Percentage of Coccolithus pelagicus vs. Reticulofenestra spp. of ODP Hole 120-747A.
216 records from Range table from planktonic foraminifers in ODP Hole 180-1115C.
29 records from Planktic foraminifera abundance of Hole 84-567.
50940 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover.
168 records from Die Teiche im Britzer Garten.
154 records from Total foraminifera counts from multinet SO119_MSN1285.
3 records from Robert Forsyth Terrestrial Gastropods Collection.
278 records from (Appendix Table 3) Distribution of live benthic foraminifera in surface sediments.
455 records from Bearded Tit National Survey in Britain 2002.
782 records from Planktic foraminifera abundance of Hole 42-372.
31000 records from Elephant Seal Sightings, Macquarie Island.
5900 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens.
170 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI.
302 records from Nannofossil abundance of Hole 66-488.
20 records from Heavy minerals of sediment core PL94-64.
131978 records from Amphibiens et Reptiles de France (Enquête 2).
1405 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México.
31 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-14.
432 records from Fishes in MZNA-VERT: ecological assessment of the Guadalope river in Aliaga (Spain).
2 records from Microzooplankton abundance and biomass at station TT054_24-22.
76 records from Phytoplankton abundance and species composition in the North Balearic Sea in April 2003.
1452 records from Nannofossil abundance of Hole 30-286.
2476 records from Range table from benthic foraminifers in ODP Hole 154-929A.
4 records from Planktic foraminifera abundance of Hole 54-424.
233 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/045-9.
45 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Fannich Hills SSSI.
245 records from Biodiversity Survey of Echuya forest, Year 2012.
53 records from Nannofossil abundance of Hole 7-63.
1215 records from (App 4) Relative contents of benthic foraminifera species in Holocene sediments from Core BP00-07/05.
59666 records from Derek Lott Coleoptera Dataset.
2 records from Données de Lépidoptères de Bruno DAUGET - Dépt des PYRENEES-ORIENTALES (66).
1520 records from (Table 16) Benthic foraminifera in Eocene-Oligocene sediments of DSDP Hole 90-593.
2662 records from PINK - Dragonfly (Odonata) monitoring for the permanent surveillance of coastal areas in Flanders, Belgium.
41 records from Planktic foraminifera counts of sediment core V28-128.
89 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB07 in the euphotic zone of the Aegean Sea in spring 1997. Part 3 - coccolithophores and other groups.
2685 records from Likona Invertebrates.
2262 records from Larval fish at time series station Helgoland Roads, North Sea, in 2005.
127026 records from Dorset Sites of Nature Conservation Interest (SNCI) species records pre 2000.
86 records from Antarctic Euphausiacea occurence data from Polish FIBEX expeditions.
68 records from Planktic foraminifera abundance of Hole 2-11.
334 records from Assemblage of living benthic foraminifera in sediment core GeoB3712-1.
257 records from Nannofossil abundance of Hole 7-62A.
3180 records from Amphibiens de Guyane.
8 records from Distribution of meiobenthos in sediment core M23_199 (2) of the northeastern Atlantic (Table 1).
182 records from Planktic foraminifera abundance of Hole 62-465.
16572 records from Visdoorgangen - Fish passage places in Flanders, Belgium.
51 records from Total foraminifera counts from M35/1_MSN1052.
29 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5112-4.
30 records from Nannofossil abundance of Hole 9-82.
1964 records from Nannofossil abundance of Hole 75-530A.
16 records from Planktic foraminifera abundance of Hole 19-184.
24 records from Planktic foraminifera abundance of Hole 20-200A.
142 records from Planktic foraminifera abundance of Hole 32-313.
38 records from BB-Biodiversität a.
7248 records from DBRC Hemiptera species records 1969 to 2015.
185 records from (Table 8) Relative abundance of benthic foraminifera in ODP Hole 112-682A, Part I.
1857 records from Censo de aves acuáticas nidificantes de la Comunidad Autónoma del País Vasco.
2307 records from Data on animal species in the Biosphere Reserve of W Bénin. Data mobilized in the framework of JRS Biodiversity Foundation funded project in Benin.
78040 records from Stackpole National Nature Reserve Species Inventory and Ad-hoc Sightings from Across Pembrokeshire.
1357 records from (Table 9) Benthic foraminifera in early-middle Miocene sediments of DSDP Hole 90-591B.
2163 records from Range table from silicoflagellates, ebridians and actiniscidians in ODP Hole 151-908A.
85 records from Birdrace-Halsbandschnäpper-Stuttgart.
14 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD59.
3350 records from Dorset SW Pilot species dataset.
11 records from Benthic macrofauna abundance of sediment core 13077-087.
420 records from (Table 2e) Nannofossil distribution chart of petroleum well Leeuwin-1.
414 records from Distribution of planktic foraminifera in sediment core GIK23071-5.
5511 records from (Appendix 2) Stratigraphic distribution of key and potential stratigraphic calcareous nannofossil markers in the upper Campanian–Maastrichtian of ODP Hole 122-762C.
58 records from Nannofossil abundance of Hole 9-82A.
74 records from Phytoplankton abundance at station Casma_2003-04-14_1, Casma, Peru.
461 records from Nannofossil abundance of Hole 24-237.
2208 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene and lowermost Pliocene of ODP Hole 105-646B (Table 1).
528 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE262.
1853 records from HBRG Badger Dataset.
13676 records from Cumbria Non Native Invasive Species.
596 records from Lower Albian l'Arboudeysse section (Niveau Paquier) individuals per gram sediment of benthic foraminifera, in SE France.
3864875 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region).
1472 records from Census of plant species in forest gaps in the natural forest of Massi (Lama Forest reserve, South-Benin).
108 records from BIRDRACE Diesmal sehen wir mehr.
1134 records from Phytoplankton abundance at several bottle stations in May 1996, Sechura, Peru.
1346 records from Weevils of Poland.
95 records from (Table 2) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-840A.
315 records from Field Study Group of the Dutch Mammal Society (NL) - 2006 - Mammal Survey Galicica National Park, Macedonia.
11554 records from Casual records for Scottish Wildlife Trust reserves - Verified data.
12072 records from Jeu de données convention Eurovia-SPN-2012-2016.
74 records from Birdrace_Gätkes_Schergen-Helgoland.
1212 records from (Table 12) Distribution of planktonic foraminifera in the early Miocene section of ODP Hole 149-900A.
201 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/092-6.
176 records from Nannofossil abundance of Hole 58-442A.
4 records from Distribution of meiobenthos in sediment core M23_149 (2) of the northeastern Atlantic (Table 1).
143 records from Microfossil abundance of Hole 50-416A.
1 records from Microplankton counts and carbon biomass at station TT007_7-CTD76.
4 records from Microplankton abundance at bottle station SEPT-1999-K7.
115 records from Observations individuelles.
232 records from Pollen analysis of sediment profile BLA00 from Blankensee.
2089 records from (Table T1) Planktonic foraminifera abundance of ODP Site 170-1039 sediments.
7 records from Données naturalistes d'Olivier VILLEPOUX.
106 records from Nannofossil abundance of Hole 73-521.
274 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto29-38.
80 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM3.
1 records from Graureiher in Lans.
5 records from Description of lithologic section units of IODP Hole 325-M0046A.
4166 records from Badger and Habitats Survey of Ireland.
7044 records from North East Scotland Mosses and Liverworts (1950-2014).
8 records from Abundance and carbon biomass of phytoplankton at station TT007_5-CTD51.
1376 records from Bird Monitoring 2017, Meise Botanic Garden.
84 records from (Tab. 11) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 32-304, Japanese Magnetic Lineations east of Japan.
636 records from 10. GEO - Tag der Artenvielfalt 2008 - LSG "Pfarrhübel" Chemnitz.
1642 records from Hypogean macro-Crustacea records.
209 records from Microzooplankton abundance measured on water bottle samples at station PS58/042-2.
722 records from Heritage Trees of Ireland.
209 records from Rescate de epífitas Oleoducto Bicentenario, Tramo Araguaney - Banadía (forofitos).
184 records from Range table from planktonic foraminifers in ODP Hole 182-1129D.
44 records from Calcareous nannofossil assemblage in sediment core CIROS-1.
8058 records from ZooplanktonBeaufortSeaNOGAP1.
6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-05-10.
429 records from Distribution of agglutinated foraminifers in sediment core Well 6406/11-1.
103 records from Plasm bearing foraminifera counts of multinet POS200/6_MSN837.
14061 records from imr_mareano_rpsledge.
224 records from Nannofossil abundance of Hole 55-433.
8 records from RISC Non-Native Species Records for Zebra Mussel.
151 records from (Tab. 9.B) Presence and abundance of benthic fauna at station FINO 1 in 2005-2007.
844 records from (Table 2) Relative abundance of 13 species of planktonic foraminifers of sediment core GIK17938-2.
50 records from Leben in den Elbwiesen.
71 records from (Data S1) Palynology of ODP Site 113-696.
115 records from Range table from benthic foraminifers in ODP Hole 149-899B.
1061 records from Antarctic Biodiversity Studies 2006 (Ross Sea, Scott Island, and Balleny Islands) (TAN0602).
675 records from (Table 5) Planktonic foraminifer abundance of ODP Hole 162-982A.
706 records from Zukünftiges NSG Höftland/Bockholmwik.
613 records from Range table from planktonic foraminifers in ODP Hole 171-1052E.
61 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1194.
23 records from Abundance of benthos infauna at station GIK23055-1.
50 records from Site condition monitoring of lamprey in the Endrick Water SSSI and SAC, 2012.
143 records from Selected Scottish freshwater fish records from 2008-2011 (collected by SEPA).
84 records from Calcareous dinoflagellate cysts of multicorer M51/3_562-5, grain fraction < 20µm.
455 records from Línea base del medio biótico en los bosques para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguablanca -El Morro Yopal.
10 records from Benthic macrofauna abundance of sediment core 13200-017.
3132 records from (Table 6) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-708A.
68 records from Kinder- und Jugendferiendorf des Kreises Groß-Gerau - Gedern/Ober-Seemen.
936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation.
3784 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A.
1182 records from Foraminifera abundance of Hole 75-532B.
67 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental.
240 records from Museums Victoria provider for OZCAM.
127 records from Total foraminifera counts of multinet M21/2_MSN647.
217 records from Planktic foraminifera assemblage in sediment core GIK23419-8.
20187 records from Alterra (NL) - Entomofauna inventory in riverside grasslands.
928 records from (Table 1) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 119-738C on the Kerguelen Plateau, Indian Ocean.
17716 records from Plan de vertebrados de la Patagonia.
4515 records from Distribution of planktic foraminifera of sediment core M35003-4.
1108 records from (Table 2) Distribution of planktonic foraminifera in the smaller size fraction of ODP Hole 120-747A.
38 records from (Table T2) Dinoflagellate cysts and pollen/spore yield and preservation in ODP Site 188-1166.
268 records from Planktic foraminifera abundance of Hole 22-217.
304444 records from Données acquises dans le cadre de l'activité du bureau d'étude BIOTOPE (1994 - 2013).
132 records from Range table from planktonic foraminifers in ODP Hole 167-1011C.
971 records from Danielsberg (Mölltal, Kärnten).
8 records from Nannofossil abundance of Hole 39-353A.
16985 records from LPO_PACA_2017_12_18.
2 records from Vegetación vascular terrestre, entomofauna y macrofauna de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO.
246 records from Nannofossil abundance of Hole 3-15.
1804 records from NRW Regional Data: all taxa (sensitive species only), West Wales.
1558 records from (Table 3) Stratigraphic ranges of selected Oligocene planktonic foraminifers in ODP Hole 115-707A.
411 records from Pollen analysis of sediment profile KAI2 from Kaiserwinkel.
18 records from Meiofauna abundance in sediment core 12930-036.
333 records from (Table 4) Relative abundance of some planktonic foraminifera and fragmentation ratios for ODP Hole 117-728A samples.
170 records from (Table 4) Benthic foraminifera genera assemblage at DSDP Section 80-548A-11-3.
76 records from SNH Invertebrate Site Condition Monitoring 2015: Lurgie Loch SSSI.
1649 records from Benthic foraminifera abundance of Hole 47-397.
6556 records from (Appendix 2) Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system.
620 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland.
36 records from Abundance of benthos infauna at station GIK23043-2.
41140 records from Staffordshire Wildlife Trust Nature Reserves Inventory.
189 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB02 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates.
225 records from Data from ILAM surveys conducted by ARCOS in Mukura landscape for year 2016.
286 records from (Figure 2) Distribution chart of dinoflagellate cysts of Cretaceous age from ODP Hole 103-638C.
1891 records from Freshwater Pest Plants.
272652 records from Florida Keys Reef Visual Census 2007.
542 records from (Appendix A) Nannofossil stratigraphic range chart for the late Maastrichtian section of DSDP Hole 86-577A.
1914 records from (Table 3) Occurrences of planktonic foraminifers in samples from ODP Hole 105-647A.
604 records from (Table 2) Relative abundance of planktic foraminifera in Maastrichtian sediments of DSDP Hole 3-21 from the Rio Grande Rise, South Atlantic Ocean.
852 records from Range table from planktonic foraminifers in ODP Hole 139-857A.
7735 records from Abundances indices and biological traits of juvenile salmon sampled in the Oir river (France).
240 records from Landschaftspflegehof (Berlin).
9 records from Bachpatenschaft Beeke.
341 records from SPC CoFish Invertebrates Observations Niue 2005.
84 records from Total foraminifera counts from M35/1_MSN1051.
99 records from (Table 5) Vertical distribution of live benthic foraminifera in surface sediments at Bouvet Island stations.
5366 records from City of Edinburgh Natural Heritage Service - Bavelaw Marsh Bird Hide Records.
91 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 30-63 µm fraction.
64 records from Total foraminifera counts of multinet M42/3_MSN1369.
165 records from Artenvielfalt auf den Elbwiesen (Dessau).
1009 records from Données naturalistes de Daniel PAVON.
1877 records from TWIC Hedgehog Public Survey.
269 records from Range table from planktonic foraminifers in ODP Hole 155-934A.
201 records from Total foraminifera counts of multinet M21/1_MSN606.
2932 records from Assemblage of planktonic foraminifera for the last glacial maximum (LGM) in sediment cores from the South Atlantic.
694 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V28-127.
89 records from Distribution of planktonic foraminifera of sediment core SH1972_13.
17 records from Microzooplankton abundance and biomass at station NBP97-08-25-4.
188 records from Total foraminifera counts of multinet M6/7_MSN116.
17 records from Feuchtwiese am Nationalpark-Haus Neuwerk.
191 records from Lindau im Bodensee.
208635 records from Estonian Nature Observations Database.
1122 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684.
40 records from Données de Rhône-Alpes transmises par Pascal Peyrache..
91 records from Heard Island Shag Phalacrocorax nivalis census, Heard Island 1992.
165 records from Crustacés Branchiopodes Phyllopodes de France.
1588 records from (Table T2) Calcareous nannofossil abundance of ODP Hole 171B-1052A sediments.
90 records from GEO-Tag mit der NAJU des Landkreises Ahrweiler am Bausenberg.
5 records from Fledermäuse u. nachtaktive Insekten.
67 records from Admiralty Bay Benthos Diversity Data Base (ABBED). Pycnogonida..
7717 records from Chondrichthyans Of Ireland.
359 records from Inventaire malacologique du site Natura 2000 FR9301537 de la Montagne de Lure (2002, ONF/MNHN).
845 records from Phytoplankton abundance during HYDROMET cruise Hydromet90/4.
273 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto1-10.
580 records from Planktic foraminifera counts of sediment core V25-59.
164135 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2014.
93 records from (Table 3) Oxygen and carbon isotope ratios of Globigerinoides sacculifer of ODP Hole 134-828A.
1174 records from Sudeniederung (Amt Neuhaus).
2318 records from DREAL_PACA_-_N2000_-_Syndicat_Mixte_d'Aménagement_de_la_Vallée_de_la_Durance_2017_12_18.
2 records from Planktic foraminifera counts of multinet PS2616-5.
135929 records from Bryophyte data for Great Britain and Ireland from the British Bryological Society held by BRC: data compiled post-Atlas.
666 records from O Tu Wharekai algae survey.
18 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2445-2.
196 records from Range table from benthic foraminifers in ODP Hole 171-1052E.
48 records from Planktic foraminifera abundance of Hole 47-397.
39549 records from Fife Nature Records Centre combined dataset.
8 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD13.
217 records from 5.Tag der Artenvielfalt: Thema Stadtbiotope.
635 records from CG04_2017_12_18.
148 records from Total foraminifera counts of multinet M21/1_MSN611.
280 records from Faberpark (Nürnberg/Stein).
33 records from Microzooplankton abundance and biomass at station TT045_15-2.
651 records from Vertebrates (except birds, INNS and restricted records), Outer Hebrides.
10159 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs.
79 records from ECOLINC: BIODIVERSITY OF THE WESTERN VOLCANIC PLAINS SIGHTINGS.
1128 records from (Table 1) Distribution of calcareous nannofossils in ODP Hole 113-689B.
42 records from (Table 1) Abundance, wet biomass, and carbon biomass of all major groups of phytoplankton in the water column of the Kara Sea.
441 records from Relative abundance of planktic foraminifera in sediment core RC08-39.
16505 records from Database for alien invasive plants occurrences in Germany.
1184 records from Evaluación y monitoreo de manglar en la Reserva de la Biósfera Los Petenes con énfasis en criterios de sustentabilidad y desarrollo.
113 records from Tornoer Teich.
71 records from Birdrace-NAJU_Aspach-Rems/Murr.
1151 records from Distribution of calcareous nannofossils from IODP Hole 313-M0027A.
64 records from Actualización e incremento del banco de datos de la colección de herbario del Jardín Etnobotánico de Oaxaca.
533 records from Benthic foraminifera abundance of Hole 84-567A, Part 1.
84 records from Benthic foraminifera abundance of Hole 84-566C.
800 records from (Appendix 2) Absolute abundance of nannofossils in ODP Hole 183-1135A.
2462 records from Waarneming.nl (NL) - Great Grey Shrike Count 2011-2012.
23 records from Nannofossil abundance of Hole 58-442B.
234 records from (Table 6) Benthic foraminiferal genera in DSDP Core 95-612-5.
50946 records from National Biodiversity Data Bank. Observation records, 1900-2014.
395 records from Données naturalistes d'IFRECOR (pf).
347 records from Données naturalistes de Delphine MONTAGNE.
80 records from 20th century Betula pubescens ssp. czerepanovii tree- and forest lines in Norway.
55291 records from Global Lacustrine Diatoms.
83 records from VFD-H: Heidenrod: Pferdeweide Mürth.
56 records from Total foraminifera counts of multinet M21/4_MSN720.
1768 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase.
405 records from Catch related distribution of Appendicularia at station M9_A near the Great Meteor Bank, Northeast Atlantic (Table 7).
104 records from Range table from benthic foraminifers in ODP Hole 172-1059B.
426 records from Données du Centre de la mer de Biarritz.
95 records from Range table from benthic foraminifers in ODP Hole 172-1059A.
401 records from Planktic foraminifera counts of sediment core RC09-162.
16 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2187-5.
185 records from Total foraminifera counts of multinet M21/2_MSN657.
91 records from Nottekanal, Klasse 7 - 10.
597 records from Percentages of planktonic foraminifera species in sediment core V30-40.
595 records from Nannofossil abundance of Hole 37-333.
92 records from Syndicat_Mixte_de_Défense_des_Berges_de_l'Asse_2017_12_18.
51 records from Phytoplankton abundance at station Sechin_2003-12-10_2, Casma, Peru.
4374 records from Inventaire des Mollusques Sphaeriidae de France.
707 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during LITTORINA cruise LI1986/1.
3030 records from (Figure 2) Quaternary biostratigraphy and planktonic foraminifera of DSDP Hole 72-517.
78 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1389.
1409 records from Diatom assamblage in samples from sediment trap OG5.
255 records from (Table 3) Occurrences of ostracodes in ODP Hole 122-763B.
678 records from (Table 2) Planktonic foraminiferal abundances in samples spanning the first appearance datum Globorotalia inflata at DSDP Hole 80-548.
6679 records from Données issues du dispositif de Biosurveillance des Retombées Atmosphériques Métalliques par les Mousses (BRAMM).
50 records from Flora und Fauna im Brexbachtal.
1 records from Sungei Buloh - Mangrovenwald.
199 records from Planktic foraminifera counts of sediment core RC09-150.
190 records from Herpetofauna laguna El Tinije.
91 records from Zwei Flüsse - eine Stadt (Villingen-Schwenningen).
6383 records from RSPB Reserves breeding bird surveys.
123 records from Birdrace-Professorenteam-Münster.
6323 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán..
2042 records from (Table 10) Distribution of planktonic foraminifers in ODP Hole 112-688A.
131 records from Planktic foraminifera counts at CTD station PS55/083-1.
273 records from (Table 1) Neogene benthic foraminiferal community at DSDP Hole 95-612.
500 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe.
1 records from Registros biológicos Parcela permanente HATOVIAL SAS en Barbosa, Antioquia.
126 records from Pollen profile II/B at Krumbach, Germany.
60 records from Hochschule Zittau/Görlitz.
18 records from Meiofauna abundance in sediment core 12930-029.
40316 records from Clyde Breeding Bird Tetrad Atlas 1985 - 1991 - non-sensitive species.
43610 records from SBC LTER Darwin Core Archive: Kelp Forest Reef Fish Abundance.
164 records from Nannofossil abundance of Hole 24-235.
28 records from Nationalpark Harz Schul-AG Braunlage.
12844 records from Israeli Butterfly Monitoring Scheme (BMS-IL).
1067 records from (Table T3) Planktonic foraminiferal stratigraphy of ODP Hole 173-1068A sediments.
140 records from Inventaire de la faune aviaire et de l'Ichtyofaune de la mare de l'Abarkaizé et des Oiseaux de Dan Saga.
23 records from AKG-Gelände in Bensheim.
38 records from Was lebt in der Brutzwiese?.
61 records from Phytoplankton abundance at station Sechin_2003-07-15_2, Casma, Peru.
2 records from Nannofossil abundance of Hole 4-26A.
96 records from Planktic foraminifera abundance of Hole 22-212.
28 records from Biodiversity Surveys, South-east Arnhem Land.
94645 records from NRW Regional Data: all taxa (excluding sensitive species), West Wales.
44 records from Planktic foraminifera abundance of Hole 19-188.
383 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Atlantic sector of the Southern Ocean (Appendix 2).
39 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, >125 µm fraction.
6327 records from (Table 1) Dinoflagellate range chart of ODP Hole 120-748C.
86 records from Données naturalistes de Pierre-Alexis RAULT.
74 records from Range table from benthic foraminifers in ODP Hole 144-873B.
222046 records from USGS Patuxent Wildlife Research Center Seabirds Compendium.
18 records from Sarcodine counts and carbon biomass at station TT012_5-PMOC8.
108 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto).
85 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México.
49 records from VFD-H.: Rheingau: Bärstadt.
137 records from (Table 15) Calcareous nannofossil occurrences in ODP Hole 130-805C.
99 records from Streuobstwiese Stedar.
3 records from Microplankton counts and carbon biomass at station TT007_12-CTD145.
852 records from Phytoplankton abundance in surface water in November 1997, Pisco, Peru.
872 records from Relativ abundances of dead fauna of benthic foraminifera in surface sediments (Table C2.2).
12 records from Nano and microzooplankton abundance and biomass at station NBP97-01-20-3.
27 records from Microzooplankton abundance and biomass at station TT043_29-1.
386 records from Pollen profile from Achenhang.
481 records from Planktic foraminifera distribution of sediment core 75KS52.
183 records from Distribution of living benthic foraminifera in sediment cores of cruise M77 Leg 1 and 2, 63-2000 µm fraction.
42 records from Range table from planktonic foraminifers in ODP Hole 180-1110A.
70 records from EPOS3: SeaStars (Echinodermata, Asteroidea).
116 records from Foraminifera species abundances from tow TT011_11-MOC72.
12 records from Kinderwald Hannover.
64 records from Phytoplankton abundance at station Rigel_5_2005-04 in April 2005, Chipana, Chile.
1089 records from Foraminifera abundance of Hole 64-478.
338 records from Unser Schulgelände.
401 records from Carabidae of Poland.
45 records from Nannofossil abundance of Hole 3-21A.
550 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Senckenberg_04_1986.
3 records from Planktic foraminifera abundance of Hole 54-419.
142 records from Birdrace-Alte_Socken-Cuxhaven.
70 records from Total foraminifera counts of multinet M21/5_MSN731.
9847 records from Derbyshire Invasive Non-Native Species (INNS) 1900 - 2014.
110 records from Inventario de macroalgas de Bahía de Banderas: Fase I y Fase II.
1803 records from (Table 3) Dead benthic foraminifera in surface sediments from the eastern South Atlantic Polar Front region.
1124 records from Planktic foraminifera abundance of Hole 72-516F.
1 records from Benthic foraminifera abundance of Hole 96-624.
918 records from Planktic foraminifera abundance of Hole 26-253.
6 records from Abundance of benthos infauna at station GIK23065-1.
8 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-962D.
579 records from Flux data of NU2_trap (Table A1).
4 records from Planktic foraminifera abundance of Hole 17-166.
39 records from Natura 2000 Complexe de l'étang de Lindre, forêt de Romersberg et zones voisines.
2688940 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS.
11728 records from Wikiplantbase #Toscana.
16 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/312-1.
24 records from ALTERECO_2017_12_18.
693 records from Range table from ostracoda in ODP Hole 143-865B.
42 records from Schulgarten Paul-Schneider-Schule, Münster.
317697 records from BioFokus.
12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_6-CTD67.
15254 records from Anymals+plants - Citizen Science Data.
4539 records from DASSH Data Archive Centre volunteer sightings records.
1830 records from Arctic benthic invertebrate collection of the Zoological Institute of the Russian Academy of Science.
24 records from Tauchen und Meer.
53 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction 63-125 µm.
700 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2008.
3390 records from Planktic foraminifera abundance of Hole 23-219.
76 records from Biological data from the Soviet Antarctic Expedition (1955-1958).
41 records from Planktic foraminifera counts of sediment core RC17-113.
25 records from Boreonemoral regnskog i Sveio.
96 records from Total foraminifera counts of multinet M26/1_MSN845.
2 records from Range table from planktonic foraminifers in ODP Hole 144-874A.
46 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 63-125 µm fraction.
462 records from (Table 1) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-541.
35 records from Nannofossil abundance in sediment core PS1293-4.
273 records from (Table 7) Benthic foraminifera genera assemblage at DSDP Section 80-548A-22.
3560 records from Relative abundance of planktic foraminifera in sediment core GeoB1309-2.
134 records from Birdrace-Easy_Birders-Plön.
228 records from Total foraminifera counts from multinet M31/3_MSN913.
5375 records from (Table 1) Stratigraphic distribution of dinocyst taxa in ODP Site 150-902.
211 records from Nannofossil abundance of Hole 20-200.
61 records from Phytoplankton abundance at station Casma_2003-03-27_2, Casma, Peru.
47 records from Assemblage of living benthic foraminifera in sediment core SO119_MC501, 30-63 µm fraction.
4511 records from SPC PROCFish/C Invertebrates Observations Solomon Islands 2006.
38 records from Numbers and statistics of benthic foraminiferal Q-mode assemblages for the Lower Oligocene of section Poetschbichl in the Lower Inn Valley area.
5072 records from NRA River corridor survey data from 1990s - River Colne and Tributaries.
797 records from (Table1) Living and dead benthic foraminifera abundance in sediments of the Bottsand-Lagoon, Western Baltic Sea.
379 records from Distribution of ostracoda in the Arctic Ocean (Table 1).
118 records from Pseudoscorpions of Ireland.
167 records from Total foraminifera counts of multinet M21/6_MSN776.
29703 records from Société_Française_d'Odonatologie_2017_12_18.
1854 records from (Table 2) Distribution of planktonic foraminifera in the upper Turonian-lower Campanian succession in ODP Hole 122-763B, Part III.
555 records from Cnidarians of Iran.
791 records from Données naturalistes de Stéphane ORIO.
243 records from WildesMoor bei Schwabstedt.
395 records from Diatom abundance measured on water bottle samples at station PS58/046-3.
1343 records from Planktic foraminifera abundance of Hole 34-319.
2 records from Description of lithologic section units of IODP Hole 325-M0052A.
9366 records from ZooplanktonBeaufortSeaNOGAP2.
3118 records from Polychaetes in surface sediments off Sylt collected during HEINCKE cruise HE258.
13 records from Microzooplankton abundance and biomass at station NBP97-08-23-6.
150 records from Abundance of planktic foraminifera at CTD station M39/4_381CTD-34.
1373 records from Aves de fragmentos de Bosque seco en la región del Caribe Colombiano.
3 records from Distribution of Quinqueloculina sp. in sediment core 13077-093.
26 records from Microzooplankton abundance and biomass at station TT045_26-3.
1419 records from Diversity of algae in wetlands.
1 records from Données naturalistes de Marcel CRUVEILLIER.
366 records from Weinberg Reichersdorf.
2 records from Distribution of Quinqueloculina sp. in sediment core 12930-084.
751 records from Range table from planktonic foraminifers in ODP Hole 157-954A.
559 records from DREAL_PACA_-_N2000_-_GIP_Calanques_2017_12_18.
72 records from Données sur les Opisthobranches et Planaires de Mayotte.
1508 records from Relative abundance of planktic foraminifera in sediment core GeoB1523-1.
562 records from Range table from benthic foraminifers in ODP Hole 189-1169A.
128 records from Planktic foraminifera abundance of Hole 94-611.
10 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Taynish Woods SSSI.
1225 records from (Table T5) Benthic foraminifer occurrence in ODP Hole 183-1139A sediments.
3 records from Abundance of zooplankton in the Aral Sea.
11 records from Données de Lépidoptères de Bruno DAUGET - Dépt du LOIR-ET-CHER (41).
330 records from Pollen analysis of sediment profile NI0 from Niklassee.
7 records from Range table from planktonic foraminifers in ODP Hole 159-959D.
1449 records from Phytoplankton abundance in surface water during cruise CD61.
29 records from Total foraminifera counts of trap L3_92_45.
2002 records from Inventaire des Coléoptères Longicornes des Antilles françaises.
130 records from (Table 15) Distribution of ostracode species in Core PS51/135-4.
115 records from Plasm bearing foraminifera counts of multinet M21/1_MSN614.
144 records from (Table 1) Benthic foraminiferal distribution at ODP Site 127-794.
2518972 records from Suffolk Biodiversity Information Service (SBIS) Dataset.
2335 records from Données du programme 50000 observations pour la forêt.
3155 records from (Appendix B) Stratigraphic occurrence of radiolarian special and species groups in sediments of ODP Hole 199-1218A.
105 records from Total foraminifera counts of trap L2_92_A42.
8 records from Microzooplankton abundance and biomass at station TT054_7-18.
1170 records from Département_du_Var_2017_12_18.
127 records from Wildlife Observations Bardon Hill 31.5.09.
31 records from Projekt Wahner Heide.
1193 records from ACCDC: Rare Species in Atlantic Canada and Adjacent Marine Waters.
153 records from (Table 1) Abundance of the main species of benthic Foraminifera in the assemblage Cribrostomoides subglobosus-Tritaxis nana of the Kara Sea.
5 records from Planktic foraminifera counts of multinet M21/4_MSN724.
196 records from Inventaire malacologique du site Natura 2000 FR9301547 du Grand Coyer (2007, ONF/MNHN).
4203 records from SPC CoFish Fish Observations Federated States of Micronesia 2006.
141 records from (Table 2) Dissolution index (XDX) values and average test mass for four species of planktonic foraminifera.
268 records from Woodland Survey.
2058 records from Table A3. Benthic foraminifera assemblage of sediment core GeoB1710-3.
310 records from Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert sowie Umland.
10320 records from HBRG Other Invertebrates Dataset.
24 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-03, 63-125 µm fraction.
233 records from Nannofossil abundance of Hole 10-95.
569 records from Macro benthos in surface sediments sampled during POLARSTERN cruise ANT-XXIII/8.
21663 records from Monitoring data from the federal state Saxony-Anhalt (Germany).
313 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_93MC.
49124 records from Finnish Floristic Database (Literature Sources).
159 records from Stable isotope analysis on sediment core PS2644-2.
2082 records from (Appendix B) Distribution of planktonic foraminifera at DSDP Hole 72-518.
203 records from Total foraminifera counts of multinet M21/1_MSN604.
214 records from Phytoplankton abundance at bottle station GOM6/1.
12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_11-CTD132.
117 records from Naturschutzgebiet Lochbusch-Königswiesen.
1441 records from Données naturalistes de Philippe GOURDAIN (ANVL).
270 records from BIRDRACE Niederlausitz-Team.
86 records from Range table from benthic foraminifers in ODP Hole 178-1097A.
1464 records from Planktic foraminifera abundance of Hole 18-173.
2 records from Planktic foraminifera abundance of Hole 54-421.
21135 records from SIRFF - FNE Centre-Val de Loire - Données 2015.
282 records from Vocalizaciones de aves mexicanas en análisis biogeográficos y reconstrucción filogenética.
441 records from Línea base del medio biótico en los bosques dentro de la zona propuesta para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguazula - Rincón del Soldado_Yopal.
322 records from (Table 6) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-849B.
789 records from Mollusques terrestres de Mayotte : prospections pour l'inventaire des ZNIEFF.
381 records from Priority effects of early successional insects influence late successional fungi in dead wood.
49 records from New records of snail-killing flies (diptera: Sciomyzidae) from Iran.
226 records from SNH Invertebrate Site Condition Monitoring 2013/14: River Spey - Insh Marshes SSSI.
528 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC08-145.
301 records from Aves de la expedición en lago de Tota, Boyacá - Proyecto Boyacá BIO.
38 records from Phytoplankton abundance at station Rigel_5_2005-03 in March 2005, Chipana, Chile.
14 records from Registro Herpetofauna de los Corregimientos de Juanchaco y Ladrilleros, Municipio de Buenaventura (Valle del Cauca) Septiembre de 2016.
3346322 records from Other BSBI Scottish data up to 2012.
2 records from Kirchenforst.
351 records from (Table 3) Distribution of late Cretaceous nannofossils in DSDP Hole 77-538A.
425 records from Percentages of planktonic foraminifera species in sediment core V22-38.
451 records from Données naturalistes acquises sur les sites du MNHN, en particulier du Jardin des plantes et de l'ilôt Poliveau.
61 records from Range table from benthic foraminifera in ODP Hole 199-1215B.
28 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/061-3.
3 records from Atlas de la flore de la forêt du Madrillet.
5625 records from RAVON (NL) - Network Ecological Monitoring Reptiles.
180 records from (Table 6) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides in DSDP Hole 79-545.
9597 records from Oiseaux nicheurs de France métropolitaine 1970-1975 - nidification possible.
797 records from DREAL Auvergne - Mammifères - 2015.
2610 records from (Table 2) Pleistocene nannofossil range chart for ODP Hole 134-828A.
31 records from Salud coralina de las comunidades arrecifales de la Isla Cayo Serranilla durante la Expedición Seaflower 2017 - Proyecto Colombia BIO.
690 records from Field Study Group of the Dutch Mammal Society (NL) - 2012 - Mammal Survey Galicia, Spain.
35 records from Nannofossil abundance of Hole 15-146A.
1 records from Synthèse de la Répartition des populations d'isard en 1994 (réseau Ongulés sauvages ONCFS-FNC-FDC).
4 records from Plasm bearing foraminifera counts of multinet POS231/3_MSN1335.
102 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Echinodermata.
2 records from Distribution of Quinqueloculina sp. in sediment core 13200-081.
6 records from (Table 1) Lipid and organochlorine content in blood of common eiders (Somateria mollissima) in Svalbard.
248 records from Planktic foraminifera abundance of Hole 73-521.
97 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1383.
473 records from (Table 2) Occurrence of the most abundant nannofossil taxa in middle Cretaceous sediments of ODP Leg 129 sites.
123 records from BIRDRACE Unterste Niederrhein-Rennvögel.
58 records from Mamíferos laguna El Tinije.
5546 records from DREAL_PACA_-_N2000_-_Parc_Naturel_Régional_du_Queyras_2017_12_18.
53 records from Phytoplankton abundance at station Casma_2003-06-24_2, Casma, Peru.
336171 records from Atlas of Finnish Macrolepidoptera.
78 records from BIRDRACE leucorhö statt logorrhö.
1945 records from Nannofossil abundance of Hole 15-147.
11081 records from Données naturalistes d'Anthony TURPAUD.
2652 records from (Appendix A) Stratigraphic range and relative abundance of Neogene planktonic foraminifer taxa in ODP Hole 120-747A.
22 records from (Table 4a) Abundance of microalgae in surface layer bottom sediments at Station ST-RSh-1 in the northeast Black Sea.
752 records from (Table 5) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-841A.
614 records from Distribution of lithic fragments and the planktic foraminifera Neogloboquadrina pachyderma in quaternary sediments of DSDP Hole 94-609 (Table 2).
1 records from Dinoflagellate abundance of Hole 21-207A.
449 records from (Table 6) Benthic foraminiferal community at DSDP Hole 94-611C.
49 records from Range table from planktonic foraminifers in ODP Hole 172-1060A.
113 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-94-GN3619940280200320.
100 records from BIRDRACE Stuttgart 100 trööt.
48 records from Deutsche Schule Budapest.
4 records from (Table 3) Mean plasma lipid content, and plasma PCB and OH-PCB concentration of polar bear (Ursus maritimus) mothers and cubs.
138 records from Total foraminifera counts of multinet M12/3_MSN561.
170 records from The occurrence and distribution of Najas flexilis (Slender naiad) in Loch of Craiglush, Loch of the Lowes and Loch of Butterstone.
442 records from Mokihinui project: landslide lakes.
1424 records from Polychaetes in surface sediments off Sylt collected during HEINCKE cruise HE206.
622 records from Nannofossil abundance of Hole 94-609B.
820 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Tota-Bijagual-Mamapacha.
25460 records from PPEAO - Pêches scientifiques. Peuplements de poissons des écosystèmes estuariens, lagunaires et continentaux d'Afrique de l'Ouest.
44 records from Total foraminifera counts of multinet M21/4_MSN721.
12 records from Analyses of the recent components in the sand fraction of sediment core PS1220-3.
5664 records from (Appendix A) Benthic foraminiferal assemblages in sediments of the last 550 kyr of ODP Hole 130-807A from the Ontong Java Plateau, Pacific Ocean.
12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_12-CTD139.
4 records from Range table from planktonic foraminifers in ODP Hole 174-1072A.
451 records from Planktic foraminifera abundance of Hole 23-220.
516 records from Base de données Pecheker. MNHN - DEPARTEMENT MILIEUX PEUPLEMENTS AQUATIQUES. Supplément.
278 records from Nannofossil abundance of Hole 26-254.
736 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments.
11 records from Analyses of the recent components of sediment core PS1012-1.
43 records from Vogelstimmenführung durch den Tiergarten.
27327 records from Données naturalistes de Pierre JAY-ROBERT.
96 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1362.
69 records from Evaluación de la presencia de 'Marmosa robinsoni' e inventario de mamíferos en el Departamento del Atlántico.
16738 records from Inventaire des Ephémères de métropole (Opie).
102 records from (Table 11) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-687A.
12 records from Nano and microzooplankton abundance and biomass at station NBP97-01-10-2.
9 records from Sarcodine counts and carbon biomass at station TT012_5-TM28.
185 records from (Table 2) Range chart of benthic and planktonic foraminifera of ODP Site 127-794.
1265 records from (Table 2) Distribution of planktonic foraminifers in ODP Site 126-790.
483 records from Artenvielfalt im Rhein-Neckar-Raum.
4498 records from Universidad de Barcelona (Facultad de Biología): Plantas vasculares del valle de Son del Pi y áreas colindantes.
4106 records from Capture Mark Recapture Data for Scottish Elasmobranchs: 2009-2018.
3151147 records from New South Wales Bird Atlassers.
13 records from Microzooplankton abundance and biomass at station NBP97-08-34-1.
1043 records from The Ecology of the Inshore Marine Zooplankton of the Chukchi Sea near Point Barrow, Alaska.
35 records from Range table from planktonic foraminifers in ODP Hole 139-857B.
48245 records from Atlas des Orthoptères et Mantides de France métropolitaine.
80 records from Nannofossil abundance of Hole 16-157.
315 records from (Table 1) Ostracoda community from DSDP Hole 95-612.
667 records from Floodplain and aquatic vegetation survey, Okavango Panhandle, 2004.
99 records from Range table from nannofossils in ODP Hole 139-855A.
21 records from Twite, winter distribution in Caithness and Sutherland 2006/7.
353106 records from Dry Tortugas Reef Visual Census 2014.
1738 records from Relative abundance of organic-walled dinoflagellate cysts in surface sediments.
26 records from Ostracoda abundance of Hole 48-406.
95 records from Range table from planktonic foraminifers in ODP Hole 146-892D.
94759 records from Monitoreo Ambiental del Proyecto La Colosa.
771 records from GEOECOLINK_2017_12_18.
122 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/567-1.
85296 records from The Scottish Squirrel Database.
96 records from BIRDRACE OAG Neuwerk.
24 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-18-1.
52 records from Pittosporum sucker (Trioza vitreoradiata) records aquired by the Royal Horticultural Society.
46 records from Planktic foraminifera counts of sediment core V26-124.
42 records from (Tab. 10) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 32-303A, Japanese Magnetic Lineations east of Japan.
34 records from Selz (Ingelheim am Rhein).
181 records from Diversidad y riqueza vegetal de los substratos rocosos del centro del estado de Veracruz.
9594 records from Disko Fan Conservation Area in the Davis Strait (Eastern Arctic) - Epibenthic Megafauna Database.
2647 records from SPC CoFish Fish Observations Nauru 2005.
144 records from Phytoplankton abundance at bottle station GOM3/1.
1143 records from Range table from planktonic foraminifers in ODP Hole 157-954B.
102 records from A Lichen Survey of the Ben Nevis Plateau.
10 records from Planktic foraminifera abundance of Hole 20-199.
1347 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2009.
2146 records from Benthos, zoo- and phytoplancton data collected during the monitoring cruise of RV "Vladimir Parshin" in 1996..
817 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V22-38.
53 records from Abundance of living benthic foraminifera in sediment core CD86_09_BC1.
265 records from Planktic foraminifera abundance of Hole 24-233.
540 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/511-12.
116 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2010.
31 records from Diatom abundance of Hole 60-453.
341 records from Size of planktic foraminifera at CTD station PS55/019.
156053 records from Miscellaneous records held by BIS.
310 records from Données naturalistes de Laurent PONCET.
19 records from Coccolith counts of multinet SO119_MSN1301.
37 records from Naturbelassene ehemalige Wiese am Haselbach (Privates Schutzgebiet).
6 records from Benthic hard-bottom communities abundance at X-Huinay, Comau Fjord, Chile, in 2010.
140 records from Range table from benthic foraminifers in ODP Hole 198-1214A.
36 records from BIOMEO_2017_12_18.
211 records from Range table from benthic foraminifers in ODP Hole 198-1209C.
841 records from Planktic foraminifera abundance of Hole 72-518.
518 records from Fishes in MZNA-VERT: monitoring program in the Suspiro stream (Spain)..
821 records from Nannofossil abundance of Hole 29-279A.
33 records from (Table 2) Distribution of early late Eocene fossil content in ODP Hole 115-714A.
78 records from (Table 10) Coiling ratio of Neogloboquadrina pachyderma of ODP Holes 127-794A and 127-197B.
114 records from Chough sightings data, Northern Ireland, 2007-2010.
661 records from Vom Gipfel ins Moor, Transekt im NSG Allgäuer Hochalpen.
1608 records from Phytoplankton abundance in surface water in February 1998, Ilo, Peru.
163 records from Lochaber wild boar/feral pig camera trap survey, 2015.
64 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >125 µm.
113 records from (Table 1) Constituents of the sand-size fraction of ODP Hole 139-856A.
22853 records from Données de Lépidoptères de Denis Vandromme.
789 records from University of Graz, Institute of Plant Sciences - Herbarium GZU.
35 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A.
488 records from Planktic foraminifera distribution of sediment core SU81-07.
926 records from Determinación del estado actual de cinco especies de cactáceas amenazadas del estado de Tamaulipas, México.
553 records from Coccolith abundence from sediment core GeoB1028-5.
11 records from ENS inventaires.
49999 records from observe_tuna_bycatch_ecoscope.
7401 records from Natural England bat roost visit records from 2013 onwards.
270 records from ACT and Southern Tablelands Weed Spotter.
41 records from Örtzemündung (Stedden).
123 records from (Table 6) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-601.
177 records from (Appendix) Ostracodes at DSDP Leg 72 Holes.
1938 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548.
30233 records from National Stag Beetle Surveys (Great Stag Hunts).
126 records from Range table from planktonic foraminifers in ODP Hole 182-1131B.
14 records from Benthic foraminifera abundance of Hole 96-620.
86616 records from Marine Offshore Seabed Survey data held by JNCC.
101 records from Nanoplankton abundance at station GeoB2006-4.
330 records from Planktic foraminifera abundance of Hole 67-499.
7 records from (Table 7) Fatty acid composition of adipose tissue from polar bears (Ursus maritimus) between 1991-2007.
569 records from Inventario de Aves Mámbita.
23 records from Ackerrain Plönhagen.
1438 records from Planktic foraminifera abundance of Hole 7-64.
1555 records from Collections of Phytoplankton at BGBM.
42995 records from Données naturalistes de Damien AVRIL.
3 records from Freies Projekt Speichersdorf - Region Oberfranken.
3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-MNB5.
1044 records from Pollen profile from Seminary School Basin.
25 records from Microzooplankton abundance and biomass at station TT043_4-1.
52 records from Benthic foraminifera and algae abundance of Hole 35-325.
162 records from Schulhof der Astrid-Lindgren-Schule Elmshorn.
313 records from BIRDRACE Gätkes Erben.
3036 records from (Table 13) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-715A.
3304 records from Benthos counted on dredged samples during Valdivia cruise VA53.
331 records from Size of planktic foraminifera at CTD station PS55/082-1.
214 records from Total foraminifera counts of multinet M21/1_MSN608.
37 records from Liether Park 2 (LMS), Klasse 6c.
385 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028.
1297 records from Recensement et distribution Mammifères marins Guadeloupe Antilles françaises (AET).
85 records from (Table 4) Ostracoda abundances in sediment core PS2212-3 (Yermak Plateau).
109 records from BIRDRACE Die Borner.
4 records from Microplankton abundance at bottle station SEPT-1999-K6.
401 records from Noble Chafer: Post-BAP records from 1998 onwards.
262 records from Variability of benthic Foraminifera north and south of the Denmark Strait.
6 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD63.
11591 records from (Table T6) Foraminifer distribution in ODP Hole 188-1167A sediments.
699 records from RISC Non-Native Species Records for Muntjac.
966 records from Foraminifera abundance of Hole 64-481A.
131 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V28-56.
17 records from Range table from benthic foraminifers in ODP Hole 189-1172D.
319 records from SNH Invertebrate Site Condition Monitoring 2013/14: Cairngorms SSSI.
44 records from Flusswerder in der Weser (Hameln).
71 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2007.
175 records from Rund um den Eichwald,Schulhof Friedrich Fröbel Gymnasium- Bad Blankenburg.
65 records from SNH Invertebrate Site Condition Monitoring 2015: Mount Bog SSSI.
371 records from Benthic foraminifera and algae abundance of Hole 81-554A.
1056 records from Diatom assamblage in samples from sediment trap OG4.
3063 records from Live (Rose Bengal stained) benthic foraminifera of surface sediments of the Persian Gulf (Table 1).
228 records from Planktic foraminifera counts of sediment core V19-201.
8 records from Abundance and carbon biomass of phytoplankton at station TT007_4-CTD48.
366 records from Diatom abundance measured on water bottle samples at station PS58/011-3.
170543 records from England Non Native Species records 1965 to 2017.
61 records from Population status, Distribution and Threats to the Nile lechwe (Kobus megaceros, M.T.Von Heuglin,1853) in the Sudd Wetland, South Sudan (2012).
134 records from (Table 3) Relative abundance of Azolla spp., peridinoid dinocysts, gonyaulacoid dinocysts, non-saccate pollen, bisaccate pollen and spores from the Lomonosov Ridge during different Arctic coring expeditions.
20 records from Nannofossil abundance of Hole 3-18.
2080 records from Non Native Species Across Wales (1989 to 2012).
8 records from Microzooplankton abundance and biomass at station TT050_17-4.
1325 records from (Appendix Table 3) Number of planktonic foraminiferal specimens within species in Late Creatceous sediments of ODP Hole 122-762C from the Exmouth Plateau, eastern Indian Ocean.
40 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/042-2.
1386 records from (Table 8) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-584.
195 records from Pedestrian mammals census in W National Park.
24095 records from BLS Rare and Threatened Lichen Records: England.
8 records from Abundance and carbon biomass of phytoplankton at station TT007_10-CTD130.
145 records from Gronau - auf der Suche nach dem Neunauge.
141 records from Plasm bearing foraminifera counts of multinet M21/1_MSN604.
1123 records from Programme national de science participative sur la Biodiversité Littorale (BioLit).
341 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V29-179.
116 records from (Table 4) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-599.
1886 records from Nannofossil abundance of Hole 94-607.
1013 records from Benthic foraminifera distribution of sediment core ASV11-987 (ASV987).
102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Ckassine*.
69 records from Entdeckertour am Muldestausee 1/05.
34 records from Nannofossil abundance of Hole 6-57A.
47 records from Range table from ostracoda in ODP Hole 159-960C.
4 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase.
43 records from Phytoplankton abundance at station Casma_2003-02-27_1, Casma, Peru.
160 records from BIOTOPE_2017_12_18.
52 records from Répertoire des espèces de poisson inventoriées dans le fleuve Niger, de Niamey à Say.
1358 records from RHS Hemerocallis midge survey.
1566 records from (Table 10) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-712A.
968 records from Caracterización florística y estructura de los relictos de bosque seco tropical en el bajo Cauca, jurisdicción Corantioquia.
1275 records from (Appendix B) Dinoflagellate cysts eco-groups of DSDP Hole 38-338.
667 records from Pollen analysis of sediment profile WE from Wesslinger See.
127 records from Inventario y monitoreo de aves silvestres en tres humedales del departamento de Córdoba.
71 records from Cabinet_Barbanson_Environnement_2017_12_18.
142 records from Planktic foraminifera abundance of Hole 32-313.
159 records from Données de Lépidoptères de Bruno DAUGET - Dépt du CHER (18).
4686 records from Butterfly_conservation_2017_12_18.
27 records from Laubwald Dreiländereck (Aachen/Vaals[NL]).
10915 records from Planktic foraminifera counts of sediment core MD95-2040.
124300 records from Cranefly (Diptera; Tipuloidea) records for Britain to 2016.
22 records from Results of palynological analysis of Hole 302-M0004B.
157 records from Total foraminifera counts from multinet SO119_MSN1286.
34145 records from Données bibliographiques et opportunistes Odonates issues du SiRF.
138 records from Artenvielfalt in der Stadt: Botanischer Garten Wuppertal und Hardt.
3429 records from Mise en place d'un suivi scientifique des amphibiens pour la production d’indicateurs de biodiversité.
480 records from Benthic foraminifera counts of sediment core GIK23342-6.
97 records from Düne am Ulvenberg (Darmstadt).
8381 records from Protected species bycatch in New Zealand fisheries.
3 records from Données naturalistes d'Emilie WEBER.
111 records from Occurrence d'ongulés et Lagomorphes de l'association Coordination Mammalogique du Nord de la France (CMNF).
48 records from Total foraminifera counts of multinet M21/5_MSN733.
7597 records from (Figure 13) Distribution of middle Miocene through middle Pleistocene planktonic foraminifera in ODP Hole 132-810C.
22 records from Coccolith counts of multinet M32/5_MSN979.
352 records from Phytoplankton abundance measured on water bottle samples at station PS65/424-3.
133 records from Grillhütte Wettsaasen, Wiese, Hecken.
10 records from Sediment properties of core PLG95B_01BOXG.
130 records from Plasm bearing foraminifera counts of multinet M21/1_MSN607.
1059 records from Planktic foraminifera abundance of Hole 15-148.
407 records from (Table 4) Standing stock values of important species in surface sediments.
1394 records from (Table 16B) Occurrences of planktonic foraminifers in DSDP Holes 90-594 and 90-594A.
94 records from (Table 2) Biomass of benthos and different animal groups in the Scotia Sea.
260 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE206.
23775 records from Données Opie, Coléoptères saproxyliques.
4 records from Distribution of Quinqueloculina sp. in sediment core 13077-087.
133 records from Abundance of radiolaria at station LV28-4-1.
32 records from Nannofossil abundance in sediment core PS1312-4.
7676 records from Distribución y abundancia de aves marinas y acuáticas en regiones marinas prioritarias y áreas protegidas del Golfo de California y Golfo de México.
17 records from Microplankton counts and carbon biomass at station TT008_5-CTD61.
2056 records from Terrestrial mammals of Dobrogea Region, Romania.
2400 records from (Table T2) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1136A.
5649 records from USGS South Florida Fish and Invertebrate Assessment Network Harvest.
257 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment II deployed at station PS64/475-1 during ARK-XIX/3c.
11640 records from Bottom Trawl Surveys: Catch and Effort Data For South East Australia, 1898-1996.
1025 records from Nannofossil abundance of Hole 49-407.
243 records from (Table 1) Oligocene benthic foraminifers abundance in ODP Hole 124-767B.
91 records from Range table from benthic foraminifers in ODP Hole 139-856A.
5074 records from SPC PROCFish/C Fish Observations Papua New Guinea 2006.
2123 records from Distribution of dinoflagellate cysts in Eocene-Oligocene sediments of DSDP Hole 38-338.
10293 records from Expédition Karubenthos 2012 : inventaire des Mollusques et des Crustacés de la Guadeloupe.
2398 records from (Appendix B) Stratigraphic range and relative abundance of Neogene planktonic foraminifer taxa in ODP Hole 120-748B.
654 records from Abundance of nanoplankton in sediment core GeoB1028-5.
123 records from Benthic foraminifera abundance of Hole 56-435A.
969 records from Caracterización biológica en la Serranía de San Lucas 2015.
392 records from Nannofossil abundance of Hole 22-217.
2 records from Benthic macrofauna abundance of sediment core 12930-022.
42 records from (Table 4) Foraminiferal species in DSDP Sample 78-541-8-3,141-143 and Section 78-541-8-CC.
135 records from Boreonemoral regnskog på østsiden av Lygrespollen.
146 records from BIRDRACE VdW Wilder Westen.
621 records from Données naturalistes de Noëlie TAPKO.
26 records from Liste des oiseaux de BZM Belambo.
1532 records from (Table 5) Ranges of benthic foraminifers from the late Oligocene to the early Miocene in ODP Hole 115-714A.
655 records from Data collected on animal species through census using Kilometric Abundance Index (KAI) in Biosphere Reserve of W-Bénin. Data mobilized in the framework of JRS Biodiversity Foundation funded project in Benin.
72 records from Range table from planktonic foraminifers in ODP Hole 180-1108B.
3 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires.
47 records from Total foraminifera counts of multinet M21/4_MSN703.
1590 records from Relative abundances of twenty-eight dominant benthic foraminifera species of DSDP Hole 23-219 (Table 1s).
110 records from (Table 5) Live benthic foraminifera in sediment core SO130-236MC.
3965 records from SPC PROCFish/C Fish Observations French Polynesia 2003, 2004 and 2006.
106 records from BIRDRACE Die Göttinger Sozialbrachvögel.
12520 records from Borders Backyard Biodiversity.
1547 records from Digitalización de la Biblioteca de Sonidos Naturales del Museo de Zoología, Facultad de Ciencias, UNAM.
398 records from (Table 3) Relative abundances of benthic foraminifera in ODP Hole 105-646A.
61 records from Wälder im Hainbachtal.
157 records from BIRDRACE Rheinische Wasserrallen.
1662 records from (Table 1) Relative abundance of planktonic foraminifers in ODP Hole 164-997A sediments.
270 records from Pollen data of trap CB1.
72 records from (Table III) Abundance of crustacea orders during RSS James Clark Ross cruise JR144.
791 records from (Appendix A) Pollen and spore counts at DSDP Hole 64-480.
121 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1359.
239 records from Phytoplankton abundance at station CD46_0405C#7.
1612 records from (Table 2) Distribution of planktonic foraminifers in ODP Site 112-681.
173 records from Plasm bearing foraminifera counts from M35/1_MSN1074.
2747 records from Données naturalistes de David HAPPE.
468 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE255.
1988 records from (Table 1) Planktonic foraminifera community at DSDP Hole 94-608.
111209 records from USGS South Florida Fish and Invertebrate Assessment Network Braun Blanquet.
527 records from Range table from benthic foraminifers in ODP Hole 145-887A.
107 records from Total foraminifera counts from multinet M31/2_MSN890.
33 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/011-3.
12 records from Bilder der Natur.
1051 records from Inventario y evaluación de fauna silvestre en el campo de exploración petrolera Niscota Sur.
45 records from Estimated plankton abundance at station PS63/064-6.
223 records from The Spider Collection at the Staatliches Museum für Naturkunde Karlsruhe.
505 records from Microplankton abundance in the euphotic zone of the Aegean, Levantine and Ionian Seas in March-April 1987.
103454 records from ANTAVIA TrackingKing.
655 records from Abundance of organic-walled dinoflagellate cysts of sediment core PS2082-1.
1749 records from Benthic foraminifera abundance of Hole 84-570.
867 records from (Appendix 2, Table 4) Relative abundances of benthic foraminifera in Late Quaternary sediments of ODP Hole 122-762B in the southeast Indian Ocean.
1091 records from (Table 2) Benthic foraminiferal species observed in the Quaternary samples from DSDP Hole 95-613.
556 records from (Table 2) Neogene benthic foraminifers of ODP Hole 120-748B.
1 records from Planktic foraminifera abundance of Hole 8-71.
415 records from Dinoflagellate cysts from sediment core PS2138-1.
24 records from Range table from planktonic foraminifers in ODP Hole 171-1052C.
801 records from Société_du_Canal_de_Provence_2017_12_18.
459 records from IASTracker. Invasive Alien Species database.
159 records from Planktic foraminifera assemblage in sediment core SU90-I06.
105 records from Conocimiento integral del tapir (Tapirus bairdii) y el pecari de labios blancos (Tayassu pecari) en México.
89 records from Total foraminifera counts of multinet POS247/2_MSN1384.
36 records from (Table 2) Planktonic foraminifer abundance of ODP Hole 162-907B.
105 records from Schulgarten Hans-Carossa-Oberschule.
3 records from Distribution of Quinqueloculina sp. in sediment core 13200-073.
1500 records from (Table 3) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583.
1126 records from Planktic foraminifera counts of sediment core A180-15.
256 records from (App 6) Relative contents of benthic foraminifera species in sediments from Core PS2718-6.
26 records from Corvids Literature Database.
14 records from City of Edinburgh Natural Heritage Service - Bumblebee Walk.
184 records from Klasse 3a.
12 records from Ohemoor (Hamburg/Norderstedt).
54 records from Phytoplankton abundance at station Rigel_4_2005-02 in Febraury 2005, Chipana, Chile.
361 records from (Appendix 4, Table 4) Relative abundances of benthic foraminifera in Late Quaternary sediments of core RC09-150 in the southeast Indian Ocean.
9 records from Range table from planktonic foraminifers in ODP Hole 183-1136A.
73 records from Benthic foraminifera abundance of Hole 80-550.
692 records from (Figure 1) Silicoflagellates at DSDP Hole 69-504.
6517 records from FBIP:IZIKO-UCT:Historical Invertebrates (1930-1980).
564 records from Atewa Range Forest Reserve Bryophytes dataset, Ghana.
7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa)..
1222 records from National Museum Of Marine Science & Technology.
1505 records from Pollen record of sediment core Bokanjacko Blato 1.
826 records from Seasearch Pink Sea Fan, Eunicella verrucosa, Survey.
319 records from Range table from benthic foraminifers in ODP Hole 144-874B.
307 records from (Table 2) Lithic grain and foraminifera shell counts in sediment core SU90-08.
613 records from Données acquises via le réseau du CBNBP.
57748 records from DASSH Data Archive Centre Academic Surveys.
18 records from Assemblage of living benthic foraminifera in sediment core CD145_55808#3, >150 µm.
230 records from (Table 10) Planktonic foraminifer abundance of ODP Site 162-986.
3 records from Distribution of Quinqueloculina sp. in sediment core 13077-019.
148 records from Freiburger GEO-Tag der Artenvielfalt am Moosweiher in Freiburg und im angrenzenden Mooswald.
466641 records from ECNASAP - East Coast North America Strategic Assessment.
215823 records from Dry Tortugas Reef Visual Census 2006.
5257 records from Données naturalistes de Philippe GOURDAIN.
18776 records from Données sur la chasse Parc amazonien de Guyane.
109 records from Exkursion Ebertsheimer/Grünstädter Berg.
97 records from Biological data measured on water bottle sampels at station AT_II-119/5_26-4.
127 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/014-4.
75 records from BIRDRACE Die Kartoffelsäcke.
3012 records from Fishes in MZNA-VERT: distribution of freshwater blenny in the Segre and Susia rivers (Spain).
11 records from Données naturalistes de Thibault RAMAGE.
1839 records from Liste des récoltes par Herbier de dépôt TOGO.
24 records from Kaisertal.
16 records from Microplankton abundance at Station MARCH-1997-GN36199704603MNB03 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms.
75 records from Naturpark Kottenforst-Ville 19.6.09.
38 records from Status and spatial diversity of Sorghum wild species in Malawi..
52726 records from ATBI Parc national du Mercantour / Parco naturale Alpi Marittime.
92 records from Birdrace-Team_BO-bachter-Bochum.
1586 records from Obs
Keywords: GBIF; biodiversity; species occurrences